Recycled water-absorbent resin and method for producing the same
Patent Information
- Application Number
- JP2023130472
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2025-02-21
AI Technical Summary
【0025】 本発明の一態様によれば、特に使用済み吸収性物品から回収された、尿等の被吸収液を吸収して膨潤した吸水性樹脂をリサイクルする場合にも、アクリルアミドが検出限界未満であるリサイクル吸水性樹脂及びその製造方法を提供できるとの効果を奏する。
Smart Images

Figure 2025025591000001 
Figure 2025025591000002 
Figure 2025025591000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a recycled water-absorbent resin and a method for producing the same. [Background technology]
[0002] 2. Description of the Related Art In absorbent articles such as disposable diapers, sanitary napkins, and incontinence pads, water-absorbent resins are widely used as water-absorbents from the viewpoint of absorbing body fluids.
[0003] Absorbent articles are generally disposable, but in recent years, from the viewpoint of resource saving and CO2 reduction, various recycling methods have been proposed for water absorbent resins recovered from used absorbent articles or waste generated in the manufacturing process of water absorbent resins, which have been conventionally discarded. Examples of recycling methods include a recycling method (material recycling in which the water absorbent resin is recycled as is) in which the water absorbent resin, which has been recovered from used absorbent articles and swelled by absorbing the liquid to be absorbed, is washed and sterilized to obtain a recycled water absorbent resin. In addition, a method (chemical recycling) has been developed in which the water absorbent resin is once solubilized to obtain a solubilized product, and a liquid containing the solubilized product is added as a part of the raw material to a monomer constituting the water absorbent resin and polymerized to produce a recycled water absorbent resin (for example, Patent Documents 1 to 4). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. WO2020 / 213298 [Patent Document 2] International Publication No. WO2022 / 080342 [Patent Document 3] International Publication No. WO2021 / 044690 [Patent Document 4] International Publication No. WO2021 / 257431 Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the above-mentioned conventional techniques, the present inventors have found that, particularly when recycling a water absorbent resin that has been recovered from a used absorbent article and has swelled by absorbing a liquid to be absorbed such as urine, there is a problem that acrylamide, which is an impurity not contained in a normal (non-recycled) water absorbent resin, may be contained in the recycled water absorbent resin on the order of several ppm.
[0006] An object of one aspect of the present invention is to provide a recycled water-absorbing resin having acrylamide below the detection limit, and a method for producing the same. [Means for solving the problem]
[0007] In order to solve the above problems, one aspect of the present invention includes the following configuration.
[0008] [1] A recycled polyacrylic acid (alkali metal salt)-based water-absorbent resin that uses, as part of its raw material, a recovered water-absorbent resin recovered from used absorbent articles or waste generated in the manufacturing process of water-absorbent resin, and / or its solubilized product, and that has a residual acrylamide content below the detection limit (0.1 ppm).
[0009] [2] The recycled water absorbent resin according to [1], containing at least one polyvalent metal cation selected from calcium and magnesium in a total amount of 1 ppm or more and 1000 ppm or less inside the resin.
[0010] [3] The recycled water absorbent resin according to [1] or [2], further comprising at least one selected from the group consisting of sulfites and hydrogen sulfites.
[0011] [4] The recycled water absorbent resin according to any one of [1] to [3], wherein the nitrogen content inside the resin is more than 0 and 1.0 mass % or less.
[0012] [5] The recycled water absorbent resin according to any one of [1] to [4], having a residual acrylic acid content of 300 ppm or less.
[0013] [6] The recycled water absorbent resin according to any one of [1] to [5], which has a moisture content of 3% by mass or more and 15% by mass or less.
[0014] [7] The recycled water absorbent resin according to any one of [1] to [6], which contains at least one selected from amino polyvalent carboxylic acids and amino polyvalent phosphoric acids.
[0015] [8] A method for producing a recycled polyacrylic acid (alkali metal salt)-based water-absorbing resin using, as a part of a raw material, a recovered water-absorbing resin and / or a solubilized product thereof recovered from used absorbent articles or waste generated in the manufacturing process of the water-absorbing resin, the method comprising: a polymerization step for obtaining a polyacrylic acid (alkali metal salt)-based hydrogel-like crosslinked polymer containing the recovered water-absorbing resin and / or a solubilized product thereof as a part of the raw material; a drying step for heating and drying the hydrogel-like crosslinked polymer; and, if necessary, a heat treatment step for heat-treating the polymer after the drying step, wherein the nitrogen content contained in the recovered water-absorbing resin and / or the solubilized product thereof used as the raw material is 1.0 mass % (based on solid content) or less, and the heating time at a material temperature exceeding 140°C after the drying step is 60 minutes or less.
[0016] [9] The method according to [8], further comprising an addition step of adding at least one selected from a sulfite and a hydrogen sulfite to the hydrogel-like crosslinked polymer and / or the polymer after the drying step.
[0017]
[10] The method according to [8] or [9], wherein the recycled water absorbent resin has a residual acrylic acid content of 300 ppm or less.
[0018]
[11] The method according to any one of [8] to
[10] , wherein the drying step and the heat treatment step are performed such that the water content of the polymer after each of these steps is in the range of 3% by mass or more and 15% by mass or less.
[0019]
[12] The manufacturing method according to any one of [8] to
[11] , wherein the recovered water absorbent resin and / or its solubilized product used as the raw material contains at least one polyvalent metal cation selected from calcium and magnesium in a total amount of 1 ppm to 1000 ppm inside the resin.
[0020]
[13] The method according to any one of [8] to
[12] , further comprising an addition step of adding at least one selected from amino polycarboxylic acids and amino polyphosphoric acids.
[0021]
[14] The method according to any one of [8] to
[13] , wherein the recovered water absorbent resin and / or its solubilized product used as the raw material has an ammonia-derived nitrogen content of 1.0 mass% (based on solid content) or less.
[0022]
[15] A method for producing a recycled polyacrylic acid (alkali metal salt)-based water-absorbing resin using, as a part of a raw material, a recovered water-absorbing resin and / or a solubilized product thereof recovered from used absorbent articles or waste generated in the production process of a water-absorbing resin, the method comprising: a polymerization step for obtaining a polyacrylic acid (alkali metal salt)-based hydrogel-like crosslinked polymer containing the recovered water-absorbing resin and / or a solubilized product thereof as a part of the raw material; a drying step for heating and drying the hydrogel-like crosslinked polymer; and, if necessary, a heat treatment step for heat-treating the polymer after the drying step, wherein the nitrogen content contained in the recovered water-absorbing resin and / or the solubilized product thereof used as the raw material is 1.0 mass% or less (based on solid content) and the residual acrylic acid content of the recycled water-absorbing resin is 300 ppm or less.
[0023]
[16] The method according to
[15] , further comprising an addition step of adding at least one selected from a sulfite and a hydrogen sulfite to the hydrogel-like crosslinked polymer and / or the polymer after the drying step.
[0024]
[17] A method for producing a recycled polyacrylic acid (alkali metal salt)-based water absorbent resin, which uses a recovered water absorbent resin recovered from used absorbent articles or waste generated in the production process of a water absorbent resin, and / or a solubilized product thereof as part of a raw material, comprising the steps of measuring the acrylamide content in the recycled water absorbent resin, and selecting the recycled water absorbent resin based on the acrylamide content. Effect of the Invention
[0025] According to one aspect of the present invention, even in the case of recycling a water absorbent resin that has been recovered from a used absorbent article and has swelled by absorbing a liquid to be absorbed, such as urine, an effect of providing a recycled water absorbent resin having an acrylamide content below the detection limit and a manufacturing method thereof can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] Hereinafter, the embodiments of the present invention will be described in detail. However, the present invention is not limited thereto, and various modifications are possible within the scope described, and the technical scope of the present invention also includes embodiments obtained by appropriately combining the technical means disclosed in different embodiments. In this specification, unless otherwise specified, the mass of the water-absorbing resin, etc. represents a value converted into a solid content. In addition, in this specification, "ppm" means ppm by mass. Furthermore, in this specification, "acid (alkali metal salt)" means "acid and / or its alkali metal salt".
[0027] In this specification, "EDANA" is an abbreviation for European Disposables and Nonwovens Associations. Also, "ERT" is an abbreviation for EDANA Recommended Test Methods, a European standard (almost a global standard) for measuring water-absorbent resins. In one embodiment of the present invention, unless otherwise specified, the physical properties of the water-absorbent resin are measured in accordance with the original ERT (revised in 2002 / publicly known document).
[0028] [1] Technical concept of the present invention In recycling a water absorbent resin recovered from a used absorbent article, particularly a water absorbent resin swollen by absorbing a liquid to be absorbed such as urine or blood, the obtained recycled water absorbent resin was insufficient in removing impurities and improving color tone even after being washed and sterilized.
[0029] Furthermore, even in the recycled water absorbent resin obtained by conventional chemical recycling, in addition to urine-derived impurities such as bacteria, magnesium, and calcium remaining in the recycled water absorbent resin, polyvalent metal salts (e.g., calcium chloride, etc.), organic acids (e.g., citric acid), etc. used as dehydration chemicals are likely to be mixed in, and the obtained recycled water absorbent resin is likely to have problems such as a decrease in water absorption performance, a deterioration in color tone (e.g., yellowing of the original white water absorbent resin in the recycled water absorbent resin), and a decrease in safety. Since the main use of water absorbent resins is as sanitary materials such as paper diapers and incontinence pads, there is a demand for recycled water absorbent resins with fewer impurities and improved color tone.
[0030] In the course of studying ways to solve such problems, the present inventors have found that, in addition to impurities such as calcium, magnesium, and bacteria derived from urine, and calcium and organic acids derived from dehydration chemicals, which are conventionally known as impurities in recycled water absorbent resins, recycled water absorbent resins, particularly polyacrylic acid (alkali metal salt)-based recycled water absorbent resins, contain acrylamide, which is an impurity not contained in normal (non-recycled) water absorbent resins, on the order of several ppm.
[0031] Acrylamide is a toxic and deleterious substance with a carcinogenicity rating of 1B, known to be found in high concentrations in potato chips, French fries, candied sweet potatoes, potato chips, etc., which are made by frying potatoes, which are high in carbohydrates, at high temperatures. Therefore, it is not advisable to include acrylamide in recycled water absorbent resins, which are primarily used as sanitary materials for disposable diapers, etc.
[0032] Therefore, an object of one aspect of the present invention is to provide a recycled water-absorbing resin in which acrylamide is below the detection limit, and a method for producing the same.
[0033] In order to solve the problem newly found this time, the present inventors have investigated the cause of the by-production of acrylamide, which is not used as a raw material for conventional (non-recycled) polyacrylic acid (alkali metal salt)-based water-absorbing resins. As a result, the present inventors have found that the by-production mechanism of acrylamide is due to the reaction of urine-derived nitrogen components (particularly, urea and ammonia, which is a decomposition product of urea) contained in the water-absorbing resin recovered from used absorbent articles with acrylic acid, which is a monomer constituting the water-absorbing resin. In particular, they have found that in the heating process (heat treatment in the drying process and heat treatment in the surface cross-linking process after drying, etc.) during the production of the water-absorbing resin, the urine-derived nitrogen components (particularly, urea and ammonia, which is a decomposition product of urea) undergo a dehydration reaction with acrylic acid to produce acrylamide as a by-product in the water-absorbing resin. As an example of the reaction, the reaction formula of the reaction in which acrylamide is by-produced by the dehydration reaction of acrylic acid and ammonia is shown below. H2C=CHCOOH + NH3→ H2C=CHCONH2+ H2O Based on the above findings, the present inventors have found that a recycled water absorbent resin containing acrylamide below the detection limit can be obtained by controlling the content of causative substances of acrylamide (nitrogen components (particularly, urea derived from urine and nitrogen components in ammonia) and acrylic acid) in the recovered water absorbent resin recovered from used absorbent articles, etc., and / or its solubilized product, which is used as a part of the raw material of the recycled water absorbent resin, to a low level, and controlling the heating temperature and heating time so that the heating conditions in the manufacturing process of the recycled water absorbent resin are mild so that the nitrogen components (particularly, urea derived from urine and nitrogen components in ammonia; the same applies below) do not react with acrylic acid to by-produce acrylamide, thereby completing the present invention.
[0034] [2] Recycled water-absorbent resin The recycled water absorbent resin according to one embodiment of the present invention is a recycled polyacrylic acid (alkali metal salt)-based water absorbent resin that uses, as a part of a raw material, a recovered water absorbent resin recovered from used absorbent articles or waste generated in the manufacturing process of the water absorbent resin, and / or a solubilized product thereof, and is a recycled water absorbent resin having a residual acrylamide content below the detection limit (0.1 ppm).
[0035] [2-1] Water-absorbing resin The term "water-absorbent resin" refers to a water-swellable, water-insoluble polymer gelling agent, and is not particularly limited, but refers to a commonly used water-absorbent resin having a water absorption capacity of 10 to 1000 times. More specifically, it is preferable that the water-absorbent resin before absorbing the liquid to be absorbed satisfies the physical property of CRC of 5 g / g or more as "water-swellable" specified in ERT441.2-02, and satisfies the physical property of Ext (amount of water-soluble component) of 0 mass% to 50 mass% as "water-insoluble" specified in ERT470.2-02.
[0036] The water-absorbent resin includes a polymer having a partially neutralized carboxyl group. In one embodiment of the present invention, specific examples of the recovered water-absorbent resin recovered from used absorbent articles or waste generated in the manufacturing process of the water-absorbent resin include polyacrylic acid (alkali metal salt)-based resins, polysulfonic acid (alkali metal salt)-based resins, maleic anhydride (alkali metal salt)-based resins, polyvinyl alcohol-based resins, polyethylene oxide-based resins, polyalginic acid (alkali metal salt)-based resins, starch-based resins, cellulose-based resins, (meth)acrylic acid alkali metal salt crosslinked polymers, saponified crosslinked products of (meth)acrylic acid ester-vinyl acetate copolymers, starch-acrylate graft polymers and crosslinked products thereof.
[0037] Moreover, the recycled water-absorbent resin according to one embodiment of the present invention is a polyacrylic acid (alkali metal salt)-based resin or a crosslinked product thereof.
[0038] The mass of the water-absorbent resin is a numerical value converted into solid content unless otherwise specified. However, when the mass of the water-absorbent resin contained in the used absorbent article is unknown, the mass of the water-absorbent resin can be calculated using the mass of the water-absorbent resin contained in the unused absorbent article and the general value of the water absorption ratio of the used water-absorbent resin. In addition, when the used absorbent article is a used disposable diaper in which the mass of the water-absorbent resin contained therein is unknown, the mass of the water-absorbent resin can also be calculated by assuming that the content of the water-absorbent resin (solid content equivalent value) relative to the total mass of the used disposable diaper is 3% by mass or more and 9% by mass or less. Furthermore, depending on the mass of the water-absorbent resin, suitable conditions for obtaining (recovering) the water-absorbent resin from the absorbent article can be appropriately adjusted. On the other hand, the actual content of the water-absorbent resin in the used absorbent article may differ from the mass calculated by the above-mentioned method depending on the usage state of the used absorbent article. However, even in that case, a person skilled in the art can appropriately adjust suitable conditions for obtaining (recovering) the water-absorbent resin from the used absorbent article while checking the actual decomposition state.
[0039] [2-2] Used absorbent items In this specification, the term "absorbent article" refers to an article used for water absorption. An example of the "absorbent article" is an absorbent article comprising an absorbent body containing a water-absorbing resin and a fibrous material, a top sheet having liquid permeability, and a back sheet having liquid impermeability. The absorbent body is suitably manufactured by blending a water-absorbing resin with a fibrous material, or by sandwiching a water-absorbing resin between fibrous materials and molding the mixture into a film, a tube, a sheet, or other shape. Here, examples of the fibrous material include hydrophilic fibers such as crushed wood pulp, cotton linters, crosslinked cellulose fibers, rayon, cotton, wool, acetate, vinylon, and the like. Specific examples of the "absorbent article" include sanitary materials (sanitary products) such as paper diapers, sanitary napkins, adult incontinence products (incontinence pads), and pet sheets, but are not limited thereto.
[0040] In this specification, the term "used absorbent article" refers to an absorbent article that has absorbed any liquid (absorbed liquid). For example, the term "used absorbent article" may be a used sanitary material that has been used by a consumer and absorbed bodily fluids such as urine and blood.
[0041] [2-3] Waste generated during the manufacturing process of water-absorbent resin In this specification, the "waste generated during the production process of a water absorbent resin" may be fine powder of the water absorbent resin generated during the production process of the water absorbent resin, non-standard water absorbent resin, waste containing the water absorbent resin generated during the production process, etc. The recovered water absorbent resin obtained from the waste generated during the production process of the water absorbent resin may be in the form of a hydrous gel or a powder.
[0042] [2-4] Recycled water-absorbent resin In one embodiment of the present invention, the "recovered water-absorbent resin" is a water-absorbent resin derived from a water-absorbent resin recovered from a used absorbent article or waste generated in the manufacturing process of the water-absorbent resin, and is not particularly limited as long as the water-absorbent resin and / or its solubilized product are water-absorbent resins that can be used as raw materials for recycled water-absorbent resins. Hereinafter, the "used absorbent article or waste generated in the manufacturing process of the water-absorbent resin" may be referred to as "used absorbent article, etc."
[0043] Examples of the "recovered water-absorbing resin" include (i) a water-absorbing resin separated from a used absorbent article or the like, (ii) a water-absorbing resin prepared by subjecting a water-absorbing resin contained in a used absorbent article or the like to a washing step and / or a dehydration step, (iii) a water-absorbing resin prepared by subjecting the water-absorbing resin of (i) or (ii) to at least one step selected from a drying step, a pulverization step, and a classification step, and (iv) a water-absorbing resin obtained by surface-crosslinking the water-absorbing resin of (iii). The "recovered water-absorbing resin" is not limited to the above examples, and may be a mixture of at least two or more of the water-absorbing resins of (i) to (iv). Alternatively, the "recovered water-absorbing resin" may further contain additives such as an antibacterial agent and a deodorant. Alternatively, the "recovered water-absorbing resin" may contain a water-absorbing resin contained in an absorbent article discarded before use.
[0044] [2-4-1] Water-absorbent resin separated from used absorbent products, etc. The water-absorbent resin separated from the used absorbent article may include the water-absorbent resin in the form contained in the used absorbent article. The water-absorbent resin in the form contained in the used absorbent article may be in a state of a hydrous gel in which an aqueous liquid such as urine or blood has been absorbed. Thus, the recovered water-absorbent resin may include the water-absorbent resin in a state of a hydrous gel.
[0045] Separating the water-absorbing resin from the used absorbent article means taking out the recovered water-absorbing resin from the gaps in the pulp, nonwoven fabric, etc. contained in the used absorbent article and dispersing it in the treatment liquid. The method for separating the water-absorbing resin from the used absorbent article is not particularly limited as long as the recovered water-absorbing resin can be separated from the used absorbent article, and any known method can be applied. For example, such a method includes a method of stirring a mixture of the treatment liquid and the used absorbent article. The water-absorbing resin dispersed in the treatment liquid can be recovered by a conventional solid-liquid separation means for separating soluble and insoluble substances, such as filtration, centrifugation, etc.
[0046] The treatment liquid is not particularly limited, and for example, a liquid corresponding to the cleaning water or the dehydration chemical described later can be used. Here, when the cleaning water described later is used as the treatment liquid, the separation of the water absorbent resin from the used absorbent article and the washing step described later can be carried out in parallel. In that case, the water absorbent resin is dispersed in the treatment liquid, i.e., the washing water, and then washed. Thereafter, the washed recovered water absorbent resin can be recovered from the treatment liquid by the solid-liquid separation means. In addition, when a liquid corresponding to the dehydration chemical is used as the treatment liquid, the separation of the water absorbent resin from the used absorbent article and the dehydration step can be carried out in parallel. In that case, the water absorbent resin is dispersed in the treatment liquid, i.e., the liquid corresponding to the dehydration chemical, and then dehydrated. Thereafter, the dehydrated water absorbent resin can be recovered from the treatment liquid by the solid-liquid separation means.
[0047] Furthermore, before or in parallel with the separation of the water-absorbent resin from the used absorbent article, an absorbent article crushing (cutting) step may be carried out in which the used absorbent article is crushed (cut) into crushed material (cut material).
[0048] The method of crushing (cutting) the used absorbent article is not particularly limited, and examples thereof include a method of cutting using a cutting tool such as a cutter. By carrying out the crushing (cutting) step, it is possible to easily separate each component, such as the recovered water-absorbent resin, pulp, nonwoven fabric, etc., from the used absorbent article. In addition, when carrying out the washing step and / or the dehydration step described below, it is possible to increase the contact opportunity between the water-absorbent resin in the used absorbent article and the washing water, dehydration chemicals, etc. As a result, it is possible to improve the washing effect, the dehydration effect, the speed, etc.
[0049] In addition, when the waste generated during the manufacturing process of the water absorbent resin is fine powder of the water absorbent resin or non-standard water absorbent resin, they can be used as they are as the recovered water absorbent resin. In addition, when the waste generated during the manufacturing process of the water absorbent resin is waste containing the water absorbent resin generated during the manufacturing process, the water absorbent resin can be separated from the waste containing the water absorbent resin, and the separated water absorbent resin can be used as the recovered water absorbent resin.
[0050] [2-4-2] A water-absorbent resin prepared by subjecting a water-absorbent resin contained in a used absorbent article, etc., to a washing process and / or a dehydration process. In one embodiment of the present invention, the "recovered water absorbent resin" may be a water absorbent resin prepared by subjecting a water absorbent resin contained in a used absorbent article to a washing step and / or a dehydration step. By carrying out the washing step and / or the dehydration step, it is possible to reduce impurities in the recovered water absorbent resin and nitrogen content derived from absorbed urine, etc. Therefore, when the recovered water absorbent resin and / or its solubilized product are used as a part of the raw material to produce a recycled polyacrylic acid (alkali metal salt)-based water absorbent resin, it is possible to suppress the by-production of acrylamide and obtain a recycled water absorbent resin with a detection limit or less.
[0051] The washing step and / or the dewatering step can be carried out in parallel with the separation of the water-absorbent resin from the used water-absorbent article.
[0052] In addition, when the water absorbent resin contained in the waste generated in the manufacturing process of the water absorbent resin also contains impurities, it is preferable to remove the impurities by carrying out the washing step and the dehydration step.
[0053] (Cleaning process) The washing step is a step of removing most of the impurities present between particles, on the particle surfaces, etc. of the swollen gel of the water-absorbent resin contained in the used absorbent article, etc., by using an aqueous liquid such as water, salt water, etc. The impurities are not particularly limited, and examples thereof include body fluids such as urine and blood, and dust, etc. Specific methods of the washing step include, for example, pouring washing water onto the swollen water-absorbent resin gel, immersing the swollen gel in washing water, and stirring the swollen gel while immersing it in washing water.
[0054] The washing water is not particularly limited as long as it can reduce the impurities by the washing step compared to before the treatment and does not alter the recovered water absorbent resin. The washing water is preferably one that allows the water absorbent resin to absorb and swell. This is because the impurities are easily removed when dehydrating after the water absorbent resin swells. Examples of such aqueous liquids that can be used include deionized water, tap water, distilled water, saline, and seawater. The aqueous liquid may also contain other components.
[0055] The cleaning water may be hot, ranging from room temperature to 100° C., or may be steam. When a hot aqueous liquid or a steam aqueous liquid is used as the cleaning water, not only a cleaning effect but also a sterilizing effect can be expected.
[0056]
[0213] The amount of the washing liquid used in the washing step is not particularly limited as long as the water absorbent resin can be sufficiently washed, but for example, the amount is preferably 2000 parts by mass or more, preferably 10000 parts by mass or more, and more preferably 100000 parts by mass or more, relative to 100 parts by mass of the water absorbent resin to be washed.
[0057] The number of times the washing step is performed is not particularly limited, and may be performed once or multiple times. Alternatively, for example, after the first washing step and the subsequent dehydration step are performed, a second or subsequent washing step may be performed.
[0058] (Dehydration process) The dehydration step is a step of discharging the absorbed liquid containing the impurities present inside the absorbent resin to the outside of the absorbent resin by shrinking the swollen gel of the absorbent resin contained in the used absorbent article or the absorbent resin that has been subjected to the washing step. In addition, when the washing step is performed before the dehydration step, the washing water used in the washing step may also be included in the absorbed liquid.
[0059] The dehydration step is not particularly limited as long as it is a treatment capable of reducing the water content of the swollen water absorbent resin. The dehydration step may include contacting the water absorbent resin contained in the used absorbent article or the water absorbent resin that has been subjected to the washing step with one or more selected from the group consisting of a polyvalent metal salt, an aqueous solution containing a polyvalent metal salt, an acidic liquid, a hydrophilic organic solvent, and an aqueous solution containing a hydrophilic solvent. Hereinafter, the one selected from the group consisting of a polyvalent metal salt, an aqueous solution containing a polyvalent metal salt, an acidic liquid, a hydrophilic organic solvent, and an aqueous solution containing a hydrophilic solvent that can be used in the dehydration step is also referred to as a "dehydration chemical". More specifically, the dehydration step may be performed, for example, by a method of contacting a swollen gel of a water absorbent resin with an aqueous solution containing a hydrophilic organic solvent; a method of contacting the swollen gel with an aqueous solution of a low pH (for example, 3 or less); a method of contacting the swollen gel with an aqueous solution of a polyvalent metal salt such as an aqueous solution of calcium chloride, or the like. Specific examples of contacting the swollen gel of the water-absorbent resin with these liquids include pouring the liquid onto the swollen gel, immersing the swollen gel in the liquid, stirring the swollen gel while immersing it in the liquid, etc. The dehydration step can also be carried out by a method of applying a voltage to the swollen gel using a pair of electrodes.
[0060] In the case where a swollen gel of a water absorbent resin is immersed in an aqueous solution containing a hydrophilic organic solvent, the concentration of the hydrophilic organic solvent in the aqueous solution to be immersed is preferably 35% by mass or more, more preferably 40% by mass or more, and further preferably 45% by mass or more.
[0061] The hydrophilic organic solvent is an organic solvent having a solubility of 20 g or more in 100 mL of water at 20° C. More preferably, the solubility is 25 g or more in 100 mL of water at 20° C., and even more preferably, the solubility is 30 g or more in 100 mL of water at 20° C.
[0062] Examples of such hydrophilic organic solvents include (1) lower alcohols, such as methanol, ethanol, n-propyl alcohol, isopropyl alcohol, tert-butyl alcohol, etc., (2) ketones, such as acetone, methyl ethyl ketone, etc., (3) ethers, such as tetrahydrofuran, dioxane, etc., and (4) esters, such as methyl acetate, methyl lactate, ethyl lactate, etc. These hydrophilic organic solvents may be used alone or in combination of two or more kinds.
[0063] When the swollen gel of the water-absorbent resin is immersed in an aqueous solution with a low pH (for example, 3 or less), the pH of the aqueous solution is preferably 3 or less, and more preferably 0.5 to 2.5. In the aqueous solution, either an inorganic acid or an organic acid can be used as the acid. In the case of an inorganic acid, hydrochloric acid, sulfuric acid, etc. can be used. In the case of an organic acid, tartaric acid, glycolic acid, malic acid, citric acid, succinic acid, acetic acid, etc. can be used. These acids may be used alone or in combination of two or more.
[0064] In the case of contacting with an aqueous solution of a polyvalent metal salt, examples of the polyvalent metal salt include metal salts of calcium, magnesium, aluminum, iron, cobalt, nickel, and copper. These polyvalent metal salts may be used alone or in combination of two or more.
[0065] In the case where the recovered water absorbent resin is a used water absorbent resin contained in a used absorbent article, it is preferable to carry out the washing step and / or the dehydration step as necessary, since impurities such as urine, body fluids such as blood, etc., absorbed into the used water absorbent resin during use can be removed, and also, nitrogen content in the impurities, which is a causative substance of acrylamide by-production, can be removed.
[0066] [2-4-3] A water-absorbent resin prepared by subjecting the water-absorbent resin of [2-4-1] or [2-4-2] to at least one selected from a drying process, a pulverization process, and a classification process. In one embodiment of the present invention, the "recovered water absorbent resin" may be a water absorbent resin prepared by subjecting the water absorbent resin of [2-4-1] or [2-4-2] to at least one selected from a drying process, a pulverization process, and a classification process.
[0067] In one embodiment of the present invention, the "recovered water absorbent resin" may be, for example, a water absorbent resin prepared by subjecting the water absorbent resin of [2-4-1] or [2-4-2] to a drying step, and then, if necessary, a crushing step and / or a classification step.
[0068] (drying process) The drying step is a step of drying the water absorbent resin to reduce its moisture content. By carrying out the drying step, the resin solid content of the recovered water absorbent resin used as a raw material for the recycled water absorbent resin can be controlled within a desired range. The resin solid content can be calculated from the loss on drying (the change in mass when 1 g of the recovered water absorbent resin is heated at 180°C for 3 hours). The resin solid content is, for example, preferably 80% by mass or more, more preferably 85% by mass or more and 97% by mass or less, even more preferably 90% by mass or more and 97% by mass or less, and particularly preferably 92% by mass or more and 97% by mass or less.
[0069] In the drying step, the method for drying the water-absorbent resin is not particularly limited, and a known drying method can be applied. Examples of the method for drying the water-absorbent resin include heat drying, hot air drying, reduced pressure drying, fluidized bed drying, infrared drying, microwave drying, drum dryer drying, drying by azeotropic dehydration with a hydrophobic organic solvent, and high humidity drying using high-temperature water vapor. Among the above-mentioned drying methods, hot air drying is preferred from the viewpoint of drying efficiency, and band drying in which hot air drying is performed on a ventilation belt is more preferred.
[0070] The drying temperature (temperature of hot air) in the hot air drying is preferably 120°C or higher and 250°C or lower, more preferably 150°C or higher and 200°C or lower, from the viewpoint of drying efficiency, etc. The drying conditions other than the drying temperature, such as the wind speed of the hot air and the drying time, may be appropriately set according to the moisture content, total mass, and target resin solid content of the water absorbent resin to be dried, etc. When band drying is performed, the various conditions described in International Publication Nos. 2006 / 100300, 2011 / 025012, 2011 / 025013, 2011 / 111657, etc. are appropriately applied as drying conditions.
[0071] (Crushing process) The pulverization step is, for example, a step of pulverizing the water-absorbent resin whose moisture content has been reduced in the drying step. Alternatively, the pulverization step may be performed on the hydrogel before the drying step.
[0072] When the water absorbent resin to be subjected to the pulverization step is in a dry state, the method of pulverizing the water absorbent resin includes, for example, a method of pulverizing the water absorbent resin using a pulverizing device such as a jaw crusher, a cone crusher, an impact crusher, a roll crusher, an autogenous pulverizer, a stamp mill, a stone mill type pulverizer, a mortar, a ring mill, a roller mill, a jet mill, a pin mill, a vibration mill, a planetary mill, a bead mill, an attritor, a hammer mill, a cutter mill, etc. When the water absorbent resin to be subjected to the pulverization step is in a gel state in a hydrous state, for example, a method of pulverizing the water absorbent resin using a pulverizing device such as a batch type or continuous type double-arm kneader, a gel pulverizer equipped with a plurality of rotating agitating blades, a single screw extruder, a twin screw extruder, a meat chopper, a disperser, a homomixer, a colloid mill, a roll mill, a high-pressure jet type disperser, a rotary mill, a vibration mill, a planetary mill, an attritor, a bead mill, etc.
[0073] (Classification process) By carrying out the classification step, the shape and size (particle diameter) of the recovered water absorbent resin can be controlled within a more suitable range. As a result, when the solubilized product of the recovered water absorbent resin is used as a raw material for a recycled water absorbent resin, the time required to generate the solubilized product can be further shortened, and the deterioration of the water absorption performance of the recycled water absorbent resin produced by using the solubilized product of the recovered water absorbent resin as at least a part of the raw material can be suppressed.
[0074] In the classification step, the method for classifying the recovered water absorbent resin is not particularly limited, and a known classification method can be applied. For example, a method using a sieve with appropriate mesh size can be mentioned as a method for classifying the water absorbent resin.
[0075] [2-4-4] A water-absorbent resin obtained by surface-crosslinking the water-absorbent resin of [2-4-3] above. In one embodiment of the present invention, the "recovered water-absorbent resin" may be a water-absorbent resin obtained by surface-crosslinking the water-absorbent resin of [2-4-3] above.
[0076] In one embodiment of the present invention, the "recovered water absorbent resin" may be, for example, a water absorbent resin prepared by subjecting the water absorbent resin of [2-4-1] or [2-4-2] to a drying process, and then subjecting the water absorbent resin to a pulverization process and / or a classification process as necessary, and the water absorbent resin may be surface-crosslinked.
[0077] (Surface crosslinking process) The surface cross-linking step is a step of providing a part with a higher cross-linking density on the surface layer of the water absorbent resin of [2-4-3] (a part several tens of μm from the surface of the water absorbent resin), and is composed of a mixing step, a heat treatment step, and a cooling step (optional). The specific configurations of the mixing step, the heat treatment step, and the cooling step (optional) are the same as those of [3-1-4] described later.
[0078] [2-4-5] Properties of recycled water absorbent resin In one embodiment of the present invention, the urea content of the recovered water absorbent resin is preferably 2.0% by mass or less, more preferably 1.8% by mass or less, and even more preferably 1.6% by mass or less. If the urea content of the recovered water absorbent resin is within the above-mentioned range, the residual acrylamide content of the recycled water absorbent resin using the recovered water absorbent resin and / or its solubilized product as a part of the raw material can be reduced. In this specification, the urea content of the water absorbent resin is a value determined by the method described in the Examples section below.
[0079] In one embodiment of the present invention, the nitrogen content of the recovered water absorbent resin is preferably 1.0% by mass or less, more preferably 0.9% by mass or less, and even more preferably 0.8% by mass or less. In this specification, the "nitrogen content of the recovered water absorbent resin" means the amount of nitrogen atoms contained in the recovered water absorbent resin. If the nitrogen content of the recovered water absorbent resin is within the above range, it is preferable because the acrylamide content in the recycled water absorbent resin can be reduced. The nitrogen content contained inside the resin of the recycled water absorbent resin can be measured by gas chromatography, liquid chromatography, the indophenol method, or the like.
[0080] In one embodiment of the present invention, the absorbency under no load (CRC) of the recovered water absorbent resin is preferably 20.0 g / g or more, more preferably 25.0 g / g or more, and even more preferably 28.0 g / g or more. The higher the upper limit of the CRC, the better, but in terms of balance with other physical properties, it is preferably 60.0 g / g or less, more preferably 55.0 g / g or less. If the CRC of the recovered water absorbent resin is within the above-mentioned range, it is preferable because the CRC of the recycled water absorbent resin using the recovered water absorbent resin and / or its solubilized product as a part of the raw material can be set to a suitable range. In this specification, the CRC of the water absorbent resin is a value determined by the method described in the Examples section below.
[0081] In one embodiment of the present invention, the absorbency under pressure (AAP0.3) of the recovered water absorbent resin under a pressure of 0.3 psi is preferably 20.0 g / g or more, more preferably 21.0 g / g or more, and even more preferably 24.0 g / g or more. The upper limit is not particularly limited, but is preferably 35.0 g / g or less from the viewpoint of balance with other physical properties. If the AAP0.3 of the recovered water absorbent resin is within the above-mentioned range, it is preferable because the AAP0.3 of the recycled water absorbent resin containing the recovered water absorbent resin and / or its solubilized product as a part of the raw material can be set to a suitable range. In this specification, the AAP0.3 of the water absorbent resin is a value determined by the method described in the Examples section below.
[0082] In one embodiment of the present invention, the color tone of the recovered water absorbent resin is preferably white.
[0083] [2-5] Solubilized material of recovered water absorbent resin [2-5-1] Solubilized material of recovered water absorbent resin In this specification, the term "solubilized product of recovered water absorbent resin" refers to a product obtained by decomposing the recovered water absorbent resin. The solubilized product of the recovered water absorbent resin may be a product obtained by decomposing a water-swellable, water-insoluble recovered water absorbent resin and solubilizing it in water. Specifically, the solubilized product includes a soluble polymer that is soluble in water and is obtained by decomposing the recovered water absorbent resin. Here, the soluble polymer is a polymer that is generated by breaking bonds and / or crosslinks between monomers of a water-swellable, water-insoluble polymer that is the recovered water absorbent resin. In addition, since water is usually also supplied to the decomposition step described later, the solubilized product is usually obtained in the form of an aqueous solution. Here, the solubilized product may be a product that is entirely solubilized in water, or a partially solubilized product that includes a polymer that is not partially solubilized. In the aqueous solution of the solubilized material obtained in the decomposition step, if the solubilized material appears dissolved in water without any remaining residue visible in the water, the recovered water absorbent resin is deemed to have been decomposed into a water-soluble water absorbent resin decomposition product. The recovered water absorbent resin provided to the decomposition step is usually in a swollen state because water is also provided. Even if a part of the recovered water absorbent resin in a swollen state remains as an undissolved swollen material after the decomposition step, if the amount of the swollen material is reduced compared to before the decomposition step, at least a part of the recovered water absorbent resin is decomposed. For this reason, the aqueous solution of the solubilized material that can be generated in the decomposition step is referred to as an aqueous solution (or dispersion) of the solubilized material, even if a part of the swollen material remains undissolved. The obtained solubilized material may be used as it is in the form of an aqueous solution, or may be used after drying to form a solid material.
[0084] [2-5-2] Manufacturing method of solubilized recovered water absorbent resin The method for producing the solubilized product of the recovered water absorbent resin is not particularly limited as long as it can decompose the water absorbent resin and solubilize it in water. For example, a method for decomposing and solubilizing the water absorbent resin with a reducing agent and a transition metal ion (for example, a method described in JP 2019-131789 A); a method for solubilizing the water absorbent resin using ascorbic acid as a reducing agent under conditions of pH 4 to 7.5 (for example, a method described in JP 3146053 A); a method for solubilizing the water absorbent resin by heat treatment in the presence of an oxidizing agent (for example, a method described in JP 3091251 A); a method for solubilizing the water absorbent resin using chlorine dioxide under acidic conditions (for example, a method described in JP 2019-108639 A); a method for solubilizing the water absorbent resin using hydrogen peroxide (for example, a method described in JP 2019-108640 A); a method for solubilizing the water absorbent resin with ozone water containing ozone (for example, a method described in JP 2019-085343 A, etc.), etc. can be mentioned.
[0085] [2-5-3] Physical properties of solubilized recovered water absorbent resin In one embodiment of the present invention, the mass average molecular weight of the solubilized product of the recovered water absorbent resin is not particularly limited, but is preferably in the range of 30,000 to 1,000,000, more preferably in the range of 40,000 to 800,000. If the mass average molecular weight of the solubilized product is too low, the amount of water-soluble content of the recycled water absorbent resin produced using the solubilized product as at least a part of the raw material increases, and as a result, the water absorption properties of the water absorbent resin may decrease. If the mass average molecular weight of the solubilized product is too large, the viscosity of the solubilized product increases, and as a result, the handleability of the solubilized product may decrease.
[0086] In one embodiment of the present invention, the urea content of the solubilized product of the recovered water absorbent resin is preferably 2.0% by mass or less, more preferably 1.8% by mass or less, and even more preferably 1.6% by mass or less. If the urea content of the solubilized product of the recovered water absorbent resin is within the above-mentioned range, the residual acrylamide content of the recycled water absorbent resin using the solubilized product as a part of the raw material can be reduced. In this specification, the urea content of the solubilized product is a value determined by the method described in the Examples section below. However, when the solubilized product of the recovered water absorbent resin is an aqueous solution, the aqueous solution is added instead of the water absorbent resin in the method described in the Examples section below, and the urea content obtained is converted into the content relative to the solid content, thereby obtaining the urea content of the solubilized product.
[0087] In one embodiment of the present invention, the nitrogen content of the solubilized product of the recovered water absorbent resin is preferably 1.0% by mass or less, more preferably 0.9% by mass or less, and even more preferably 0.8% by mass or less. Here, in this specification, "nitrogen content of the solubilized product of the recovered water absorbent resin" means the amount of nitrogen atoms (particularly, nitrogen atoms derived from urea and ammonia, which is a urea decomposition product) contained in the solubilized product of the recovered water absorbent resin. If the nitrogen content of the solubilized product of the recovered water absorbent resin is within the above range, it is preferable because the acrylamide content in the recycled water absorbent resin can be reduced. The nitrogen content contained inside the resin of the recycled water absorbent resin can be measured by gas chromatography, liquid chromatography, indophenol method, etc.
[0088] [2-6] Properties of recycled water-absorbent resin The recycled water absorbent resin according to one embodiment of the present invention may be a recycled polyacrylic acid (alkali metal salt)-based water absorbent resin using the above-mentioned recovered water absorbent resin and / or its solubilized product as part of the raw material, and the manufacturing method thereof is not particularly limited, but for example, it can be manufactured by a manufacturing method for a water absorbent resin in which the above-mentioned recovered water absorbent resin and / or its solubilized product are used as part of the raw material in the manufacturing process of the water absorbent resin using the monomer constituting the water absorbent resin as the raw material. The recycled water absorbent resin according to one embodiment of the present invention has a residual acrylamide content less than the detection limit (0.1 ppm).
[0089] Here, the recycled polyacrylic acid (alkali metal salt)-based water absorbent resin means a recycled water absorbent resin that is a polyacrylic acid (alkali metal salt)-based water absorbent resin. The polyacrylic acid (alkali metal salt)-based water absorbent resin is preferably a hydrophilic cross-linked polymer obtained by cross-linking and polymerizing an acrylic acid (alkali metal salt)-based monomer. However, the total amount, i.e., 100% by mass, does not need to be the hydrophilic cross-linked polymer, and additives and the like can be contained within a range that satisfies the required performance.
[0090] The polyacrylic acid (alkali metal salt)-based water-absorbing resin is a cross-linked polymer containing 50 mol % or more of structural units derived from acrylic acid (alkali metal salt) relative to the total structural units constituting the polyacrylic acid (alkali metal salt)-based water-absorbing resin.
[0091] The polyacrylic acid (alkali metal salt)-based water absorbent resin is a crosslinked polymer obtained by using, as a raw material, preferably 50 mol % or more, more preferably 70 mol % or more, even more preferably 90 mol % or more, and preferably 100 mol % or less, more preferably substantially 100 mol % of acrylic acid (alkali metal salt), relative to the portion of the monomers involved in the polymerization reaction excluding the internal crosslinking agent.
[0092] The recycled water absorbent resin according to one embodiment of the present invention contains at least one polyvalent metal cation selected from calcium and magnesium in the resin interior, preferably in a range of 1 ppm to 1000 ppm, more preferably 750 ppm or less, and even more preferably 500 ppm or less, in terms of the total amount of the polyvalent metal cation. The recycled water absorbent resin according to one embodiment of the present invention uses as a part of the raw material a recovered water absorbent resin recovered from used absorbent articles or waste generated in the manufacturing process of the water absorbent resin, and / or a solubilized product thereof, and therefore may contain impurities contained in the recovered water absorbent resin, particularly calcium and / or magnesium derived from body fluids such as urine and blood, or dehydration chemicals used in the dehydration step, in the resin interior in a range of 1 ppm to 1000 ppm. In this specification, the term "resin interior" refers to a part excluding the surface layer of the recycled water absorbent resin (a part several tens of μm from the surface of the water absorbent resin). Calcium and / or magnesium may be added to the surface layer of the recycled water absorbent resin in a surface treatment (e.g., surface cross-linking treatment, additive addition treatment) that is carried out as necessary in the manufacturing process of the recycled water absorbent resin. However, when calcium and / or magnesium is contained in the resin interior of the water absorbent resin in the range of 1 ppm to 1000 ppm, the water absorbent resin can be considered to be a recycled water absorbent resin that uses a recovered water absorbent resin recovered from used absorbent articles or waste generated in the manufacturing process of the water absorbent resin, and / or a solubilized product thereof as part of the raw material. The calcium content and magnesium content contained in the resin interior can be measured by chelate titration, atomic absorption spectrometry, high-frequency inductively coupled plasma atomic emission spectrometry, etc.
[0093] The recycled water absorbent resin according to one embodiment of the present invention preferably further contains at least one selected from sulfite and hydrogen sulfite. By further containing at least one selected from sulfite and hydrogen sulfite, the amount of acrylic acid remaining in the water absorbent resin can be reduced. Therefore, the acrylamide content in the recycled water absorbent resin can be reduced. The total content of at least one selected from sulfite and hydrogen sulfite contained in the recycled water absorbent resin is preferably in the range of 0.0010% by mass or more and 1.0% by mass or less, more preferably 0.0030% by mass or more and 0.50% by mass or less, and even more preferably 0.0050% by mass or more and 0.30% by mass or less, relative to the recycled water absorbent resin. The content of sulfite and the content of hydrogen sulfite contained in the recycled water absorbent resin can be measured by liquid chromatography analysis. As the sulfite and / or hydrogen sulfite, monovalent salts, particularly alkali metal salts such as sodium salts and potassium salts, can be preferably used.
[0094] The recycled water absorbent resin according to one embodiment of the present invention contains nitrogen content in the resin interior that is more than 0, preferably 1.0 mass% or less, more preferably 0.9 mass% or less, and even more preferably 0.8 mass% or less. Here, the nitrogen content means the amount of nitrogen atoms (particularly, nitrogen atoms derived from urea and ammonia, which is a decomposition product of urea) contained in the recycled water absorbent resin. If the nitrogen content contained in the resin interior of the recycled water absorbent resin according to one embodiment of the present invention is within the above range, it is preferable because the acrylamide content in the recycled water absorbent resin can be reduced. The nitrogen content contained in the resin interior of the recycled water absorbent resin can be measured by gas chromatography, liquid chromatography, indophenol method, etc.
[0095] In addition, the recycled water absorbent resin according to one embodiment of the present invention contains a nitrogen content of more than 0, preferably 1.0 mass% or less, more preferably 0.9 mass% or less, and further preferably 0.8 mass% or less, in the whole including the resin interior and the surface layer.
[0096] The recycled water absorbent resin according to one embodiment of the present invention has a residual acrylic acid content of preferably 300 ppm or less, more preferably 200 ppm or less, and even more preferably 100 ppm or less. The by-production of acrylamide can be generated by the reaction of the remaining monomer component acrylic acid with nitrogen. Therefore, if the residual acrylic acid content in the recycled water absorbent resin is within the above range, it is preferable because the by-production of acrylamide in the recycled water absorbent resin is suppressed. The residual acrylic acid content in the recycled water absorbent resin can be measured by the method described in the examples below.
[0097] The recycled water absorbent resin according to one embodiment of the present invention has a moisture content of preferably 3% by mass or more and 15% by mass or less, more preferably 4% by mass or more and 12% by mass or less, and even more preferably 5% by mass or more and 10% by mass or less. The by-production of acrylamide may occur due to the reaction between the remaining monomer component, acrylic acid, and the nitrogen content. In addition, by setting the heating conditions in the manufacturing process of the recycled water absorbent resin to mild conditions, the by-production of acrylamide due to the reaction between the nitrogen content and acrylic acid can be suppressed. Therefore, it is preferable to heat the water absorbent resin under mild heating conditions so that the moisture content does not become less than 3% by mass. In addition, if the moisture content of the recycled water absorbent resin is 15% by mass or less, the moisture content is suitably reduced, and the recycled water absorbent resin is excellent in handleability, which is preferable. The moisture content of the recycled water absorbent resin can be calculated from the loss on drying (the change in mass when 1 g of the water absorbent resin is heated at 180° C. for 3 hours).
[0098] The recycled water absorbent resin according to one embodiment of the present invention preferably further contains at least one selected from amino polycarboxylic acid and amino polyphosphate. By further containing at least one selected from amino polycarboxylic acid and amino polyphosphate, the polymerization reaction of the recycled water absorbent resin using the recovered water absorbent resin and / or its solubilized product as a part of the raw material can be suitably advanced, so that the amount of acrylic acid remaining in the polymer can be reduced. Therefore, the content of acrylamide in the recycled water absorbent resin can be reduced. The content of at least one selected from amino polycarboxylic acid and amino polyphosphate contained in the recycled water absorbent resin is preferably 0.00001% by mass or more and 10% by mass or less, more preferably 0.00005% by mass or more and 5% by mass or less, and even more preferably 0.0001% by mass or more and 1% by mass or less, based on the recycled water absorbent resin, in total. The content of amino polycarboxylic acid and the content of amino polyphosphate contained in the recycled water absorbent resin can be measured by liquid chromatography analysis, IR analysis, etc.
[0099] Examples of the amino polycarboxylic acid include iminodiacetic acid, hydroxyethyliminodiacetic acid, nitrilotriacetic acid, nitrilotripropionic acid, ethylenediaminetetraacetic acid, hydroxyethylenediaminetriacetic acid, hexamethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, triethylenetetraminehexaacetic acid, trans-1,2-diaminocyclohexanetetraacetic acid, bis(2-hydroxyethyl)glycine, diaminopropanoltetraacetic acid, ethylenediamine-2-propionic acid, glycol ether diamine tetraacetic acid, bis(2-hydroxybenzyl)ethylenediaminediacetic acid, ethylenediamine disuccinic acid, L-glutamic acid diacetic acid, 3-hydroxy-2,2'-iminodisuccinic acid, glycol ether diamine tetraacetic acid, methylglycine diacetic acid, and salts thereof.
[0100] Examples of the polyphosphate include pyrophosphoric acid, tripolyphosphoric acid, tetrapolyphosphoric acid, metaphosphoric acid, and salts thereof.
[0101] When the amino polycarboxylic acid and / or amino polyphosphoric acid are in the form of a salt, a monovalent salt, particularly an alkali metal salt such as a sodium salt or a potassium salt, can be preferably used.
[0102] The absorbency against no load (CRC) of the recycled water absorbent resin according to one embodiment of the present invention is preferably 20.0 g / g or more, more preferably 25.0 g / g or more, and even more preferably 28.0 g / g or more. The higher the upper limit of the CRC, the better, but in terms of the balance with other physical properties, it is preferably 50.0 g / g or less, more preferably 45.0 g / g or less, and even more preferably 40.0 g / g or less.
[0103] In one embodiment of the present invention, the absorbency under pressure (AAP0.3) of the water absorbent resin obtained by the method for producing the water absorbent resin at a pressure of 0.3 psi is preferably 20.0 g / g or more, more preferably 21.0 g / g or more, and even more preferably 24.0 g / g or more. The upper limit is not particularly limited, but is preferably 35.0 g / g or less from the viewpoint of balance with other physical properties.
[0104] In one embodiment of the present invention, the color tone of the recovered water absorbent resin is preferably white.
[0105] [3] Manufacturing method for recycled water absorbent resin The method for producing a recycled water absorbent resin according to one embodiment of the present invention is a method for producing a recycled polyacrylic acid (alkali metal salt)-based water absorbent resin using the recovered water absorbent resin and / or its solubilized product as a part of the raw material. For example, this production method is a method in which the recovered water absorbent resin and / or its solubilized product are mixed into a part of the raw material used when newly producing a water absorbent resin. Note that "newly producing a water absorbent resin" refers to the production of a conventional (normal) water absorbent resin using a monomer constituting the water absorbent resin as a raw material.
[0106] [3-1] Embodiment 1 The manufacturing method of the recycled water absorbent resin according to the present embodiment is a manufacturing method of a recycled polyacrylic acid (alkali metal salt)-based water absorbent resin using a recovered water absorbent resin and / or a solubilized product thereof recovered from used absorbent articles or waste generated in the manufacturing process of the water absorbent resin as a part of a raw material, and includes a polymerization step of obtaining a polyacrylic acid (alkali metal salt)-based hydrogel-like crosslinked polymer containing the recovered water absorbent resin and / or a solubilized product thereof as a part of a raw material, a drying step of heating and drying the hydrogel-like crosslinked polymer, and a heat treatment step of heat treating the polymer after the drying step as necessary, in which the nitrogen content contained in the recovered water absorbent resin and / or the solubilized product thereof used as the raw material is 1.0 mass % (based on solid content) or less, and the heating time during which the material temperature exceeds 140° C. after the drying step is 60 minutes or less.
[0107] By controlling the content of nitrogen, which is a causative substance of acrylamide, in the recovered water absorbent resin and / or its solubilized product to a low level, and setting the heating temperature and heating time in the drying step and thereafter within the above-mentioned ranges so that the heating conditions in the manufacturing process of the recycled water absorbent resin are mild, a recycled water absorbent resin having an acrylamide content below the detection limit can be obtained.
[0108] [3-1-1] Polymerization process This step is not particularly limited as long as it is a step of obtaining a polyacrylic acid (alkali metal salt)-based hydrogel-like crosslinked polymer (hereinafter referred to as "hydrogel") containing the recovered water-absorbent resin and / or a solubilized product thereof as part of a raw material. For example, this step may be a step of obtaining a hydrogel by polymerizing an acrylic acid (alkali metal salt)-based monomer aqueous solution to which the recovered water-absorbent resin and / or a solubilized product thereof has been added in advance, or a step of adding the recovered water-absorbent resin and / or a solubilized product thereof at any time point during the step of polymerizing an acrylic acid (alkali metal salt)-based monomer aqueous solution and polymerizing the same, or a combination of these.
[0109] (Polymerization initiator) The polymerization initiator used in one embodiment of the present invention is not particularly limited since it is appropriately selected depending on the polymerization form and the like. For example, a thermally decomposable polymerization initiator, a photodecomposable polymerization initiator, or a redox-based polymerization initiator in combination with a reducing agent that promotes the decomposition of these polymerization initiators can be mentioned. Specifically, one or more of the polymerization initiators disclosed in U.S. Pat. No. 7,265,190 are used. From the viewpoint of the handleability of the polymerization initiator and the physical properties of the water-absorbing resin, a peroxide or an azo compound is preferably used, more preferably a peroxide, and even more preferably a persulfate. From the viewpoint of preventing the by-production of acrylamide, it is more preferable to use a polymerization initiator that does not contain a nitrogen component derived from ammonia. The amount of the polymerization initiator used is preferably 0.001 mol% or more and 1 mol% or less, more preferably 0.001 mol% or more and 0.5 mol% or less, based on the monomer. The amount of the reducing agent used is preferably 0.0001 mol% or more and 0.02 mol% or less, based on the monomer. Instead of the polymerization initiator, the polymerization reaction may be carried out by irradiation with active energy rays such as radiation, electron beams, and ultraviolet rays, or these active energy rays may be used in combination with the polymerization initiator.
[0110] (polymerization form) The polymerization form applied to one embodiment of the present invention is not particularly limited, but from the viewpoint of water absorption characteristics, ease of polymerization control, etc., preferably includes spray droplet polymerization, aqueous solution polymerization, reversed phase suspension polymerization, more preferably aqueous solution polymerization, reversed phase suspension polymerization, and even more preferably aqueous solution polymerization. Among them, continuous aqueous solution polymerization is particularly preferred, and both continuous belt polymerization and continuous kneader polymerization are applied. As specific polymerization forms, continuous belt polymerization is disclosed in U.S. Pat. No. 4,893,999, U.S. Pat. No. 6,241,928, U.S. Patent Application Publication No. 2005 / 215734, etc., and continuous kneader polymerization is disclosed in U.S. Pat. No. 6,987,151, U.S. Pat. No. 6,710,141, etc., respectively. By adopting these continuous aqueous solution polymerizations, the production efficiency of the water absorbent resin is improved.
[0111] In addition, preferred forms of the continuous aqueous solution polymerization include "high-temperature initiated polymerization" and "high-concentration polymerization". "High-temperature initiated polymerization" refers to a form in which polymerization is initiated at a temperature of the aqueous monomer solution of preferably 30°C or higher, more preferably 35°C or higher, even more preferably 40°C or higher, and particularly preferably 50°C or higher (upper limit is the boiling point). "High-concentration polymerization" refers to a form in which polymerization is performed at a monomer concentration of preferably 30% by mass or higher, more preferably 35% by mass or higher, even more preferably 40% by mass or higher, and particularly preferably 45% by mass or higher (upper limit is the saturated concentration). These polymerization forms can also be used in combination.
[0112] In one embodiment of the present invention, the polymerization can be carried out under an air atmosphere, but from the viewpoint of the color tone of the obtained water absorbent resin, it is preferable to carry out the polymerization under an inert gas atmosphere such as nitrogen or argon. In this case, for example, it is preferable to control the oxygen concentration to 1% by volume or less. It is also preferable to replace the dissolved oxygen in the aqueous monomer solution with an inert gas (for example, dissolved oxygen less than 1 mg / l). In one embodiment of the present invention, the polymerization form can also be foaming polymerization in which bubbles (particularly the inert gas, etc.) are dispersed in the aqueous monomer solution to carry out the polymerization.
[0113] (Addition of Recycled Water Absorbent Resin and / or Its Solubilized Material) In one embodiment of the present invention, the recovered water absorbent resin and / or its solubilized product may be added in at least one step selected from a polymerization step, a monomer aqueous solution preparation step described below, and a hydrous gel crushing step in the production of a recycled water absorbent resin.
[0114] The recovered water absorbent resin and / or its solubilized product may be added as is, as an aqueous solution in an aqueous liquid, or as an aqueous dispersion (slurry).
[0115] When the recovered water absorbent resin and / or its solubilized product (hereinafter sometimes referred to as "recovered water absorbent resin, etc.") are added in the "monomer aqueous solution preparation step", the recovered water absorbent resin, etc. may be mixed into the monomer aqueous solution, or the recovered water absorbent resin, etc. may be mixed in advance with water and then the monomer (or its aqueous solution) may be mixed. From the viewpoint of uniform mixing of raw materials, it is more preferable to mix the recovered water absorbent resin, etc. into the monomer aqueous solution. When the recovered water absorbent resin, etc. is added as it is and / or as an aqueous solution or aqueous dispersion (slurry), the recovered water absorbent resin, etc. and / or the aqueous solution or aqueous dispersion (slurry) of the recovered water absorbent resin, etc. may be heated to 50°C or higher before being added.
[0116] When the recovered water absorbent resin or the like is added in the "polymerization step", the recovered water absorbent resin or the like may be added as it is or as an aqueous solution or aqueous dispersion before, during, or after the start of polymerization. From the viewpoint of uniformity of the polymer component, it is preferable to add the recovered water absorbent resin or the like before the start of polymerization.
[0117] When the recovered water absorbent resin or the like is added in the "gel crushing step", the recovered water absorbent resin or the like may be added as it is or as an aqueous solution or aqueous dispersion before or during crushing. It may also be added in portions. From the viewpoint of uniformity of the gel component, it is more preferable to add the recovered water absorbent resin or the like before gel crushing.
[0118] The proportion of the recovered water absorbent resin and / or its solubilized material in the total recycled water absorbent resin raw material is preferably 1 mass % or more and 60 mass % or less, more preferably 1 mass % or more and 50 mass % or less, more preferably 1 mass % or more and 40 mass % or less, and further preferably 1 mass % or more and 30 mass % or less.
[0119] [3-1-2] Drying process This step is a step of obtaining a dried polymer by heating and drying the polyacrylic acid (alkali metal salt)-based hydrogel crosslinked polymer (hereinafter sometimes referred to as "hydrogel") obtained in the polymerization step and / or the hydrogel crushing step described below to a desired resin solid content. The resin solid content is determined from the loss on drying (the change in mass when 1 g of the water-absorbent resin is heated at 180°C for 3 hours), and is preferably 80% by mass or more, more preferably 85% by mass to 97% by mass, even more preferably 90% by mass to 97% by mass, and particularly preferably 92% by mass to 97% by mass.
[0120] The method for drying the hydrogel is not particularly limited as long as it is a method for drying by heating, and examples thereof include direct heating drying, hot air drying, reduced pressure drying, fluidized bed drying, infrared drying, microwave drying, drum dryer drying, drying by azeotropic dehydration with a hydrophobic organic solvent, high humidity drying using high-temperature water vapor, etc. Among these, from the viewpoint of drying efficiency, hot air drying is preferred, and band drying in which hot air drying is performed on a ventilation belt is more preferred.
[0121] For example, the drying temperature (hot air temperature) in the hot air drying is preferably 120° C. or higher and 220° C. or lower, more preferably 140° C. or higher and 200° C. or lower, from the viewpoints of the residual acrylamide content, color tone, drying efficiency, etc., of the resulting recycled water absorbent resin. The drying conditions other than the drying temperature, such as the hot air speed and drying time, may be appropriately set according to the water content and total mass of the hydrogel to be dried and the target resin solid content, and when band drying is performed, the conditions described in WO 2006 / 100300, WO 2011 / 025012, WO 2011 / 025013, WO 2011 / 111657, etc. are appropriately applied.
[0122] [3-1-3] Nitrogen content contained in recovered water absorbent resin and / or its solubilized product, and heating conditions in the method for producing recycled water absorbent resin according to this embodiment In the manufacturing method according to the present embodiment, the nitrogen content in the recovered water absorbent resin and / or its solubilized product used as the raw material is 1.0 mass % or less (based on solid content), more preferably 0.9 mass % or less, and more preferably 0.8 mass % or less.
[0123] In the manufacturing method according to the present embodiment, the nitrogen content derived from ammonia contained in the recovered water absorbent resin and / or its solubilized product used as the raw material is preferably 1.0% by mass (based on solid content) or less, more preferably 0.9% by mass or less, and more preferably 0.8% by mass or less. If the nitrogen content derived from ammonia is within the above range, the acrylamide content in the resulting recycled water absorbent resin can be reduced, which is preferable. Here, the nitrogen content derived from ammonia can be measured by the indophenol method.
[0124] In the manufacturing method according to the present embodiment, the heating time after the drying step during which the material temperature exceeds 140° C. is 60 minutes or less, more preferably 45 minutes or less, and even more preferably 30 minutes or less. Here, the "heating time after the drying step during which the material temperature exceeds 140° C." refers to the total heating time during which the material temperature exceeds 140° C. in the entire drying step and, if necessary, the heat treatment step in which the polymer is further heat-treated after the drying step. An example of the heat treatment step in which the polymer is heat-treated after the drying step if necessary can be the heat treatment step in the surface crosslinking step described later, but the heat treatment step is not limited to this and includes all heat treatment steps. In this specification, the "material temperature" is a value obtained by measuring the internal temperature of the material using a thermocouple or the like.
[0125] In the manufacturing method according to one embodiment of the present invention, the drying step and the heat treatment step are preferably performed so that the polymer after each step has a moisture content of preferably 3% by mass or more and 15% by mass or less, more preferably 4% by mass or more and 12% by mass or less, and even more preferably 5% by mass or more and 10% by mass or less. By setting the heating conditions in the manufacturing process of the recycled water absorbent resin to mild conditions, it is possible to suppress the by-production of acrylamide due to the reaction between nitrogen and acrylic acid. Therefore, it is preferable to heat the water absorbent resin under mild heating conditions so that the moisture content does not become less than 3% by mass.
[0126] [3-1-4] Surface crosslinking process The method for producing a recycled water absorbent resin according to one embodiment of the present invention may further include a surface cross-linking step, which is a step of providing a portion with a higher cross-linking density on the surface layer (a portion several tens of μm from the surface of the water absorbent resin) of the polymer (water absorbent resin) obtained through the drying step, and is composed of a mixing step, a heat treatment step, and a cooling step (optional).
[0127] In the surface cross-linking step, a surface-cross-linked water-absorbent resin is obtained by radical cross-linking, surface polymerization, cross-linking reaction with a surface cross-linking agent, or the like on the surface of the water-absorbent resin.
[0128] (Surface cross-linking agent) The surface cross-linking agent used in one embodiment of the present invention is not particularly limited, but may be an organic or inorganic surface cross-linking agent. Among them, from the viewpoint of the physical properties of the water-absorbent resin, the handling property of the surface cross-linking agent, etc., an organic surface cross-linking agent that reacts with a carboxyl group is preferred. For example, one or more surface cross-linking agents disclosed in U.S. Patent No. 7,183,456 may be mentioned. More specifically, polyhydric alcohol compounds, epoxy compounds, haloepoxy compounds, polyamine compounds or their condensates with haloepoxy compounds, oxazoline compounds, oxazolidinone compounds, polyvalent metal salts, alkylene carbonate compounds, cyclic urea compounds, etc. may be mentioned.
[0129] The amount of the surface crosslinking agent used (when a plurality of agents are used, the total amount used) is preferably 0.01 to 10 parts by mass, more preferably 0.01 to 5 parts by mass, relative to 100 parts by mass of the water absorbent resin. The surface crosslinking agent is preferably added as an aqueous solution, and in this case, the amount of water used is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 10 parts by mass, relative to 100 parts by mass of the water absorbent resin. Furthermore, when a hydrophilic organic solvent is used as necessary, the amount used is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the water absorbent resin.
[0130] (Mixing process) This step is a step of mixing the water absorbent resin and the surface crosslinking agent. The method of mixing the surface crosslinking agent is not particularly limited, but includes a method of preparing a surface crosslinking agent solution in advance, and preferably spraying or dropping the liquid onto the water absorbent resin, more preferably spraying and mixing.
[0131] The device for carrying out the mixing is not particularly limited, but is preferably a high-speed stirring type mixer, more preferably a high-speed stirring type continuous mixer.
[0132] (Heat treatment process) This step is a step in which heat is applied to the mixture discharged from the mixing step to cause a crosslinking reaction on the surface of the water-absorbent resin.
[0133] The device for carrying out the crosslinking reaction is not particularly limited, but preferably includes a paddle dryer. The reaction temperature (material temperature) in the crosslinking reaction is appropriately set depending on the type of surface crosslinking agent used, but is preferably 50°C or higher and 220°C or lower, more preferably 100°C or higher and 200°C or lower.
[0134] (cooling process) This step is an optional step that is carried out as necessary after the heat treatment step. The cooling device is not particularly limited, but is preferably a device with the same specifications as the device used in the heat treatment step, and more preferably a paddle dryer. This is because it can be used as a cooling device by changing the heat medium to a refrigerant. The water-absorbent resin obtained in the heat treatment step is forcibly cooled, as necessary, to preferably 40°C or more and 80°C or less, more preferably 50°C or more and 70°C or less, in the cooling step.
[0135] [3-1-5] Monomer aqueous solution preparation process The method for producing a recycled water absorbent resin according to one embodiment of the present invention may further include a monomer aqueous solution preparation step. This step is a step of preparing an aqueous solution containing acrylic acid (alkali metal salt) as a main component (hereinafter referred to as "monomer aqueous solution"). Although a monomer slurry liquid can be used within a range in which the water absorption performance of the obtained water absorbent resin is not reduced, for the sake of convenience, the monomer aqueous solution will be described in this section. Moreover, the "main component" means that the amount (content) of acrylic acid (alkali metal salt) used is 50 mol % or more with respect to the total monomers (excluding the internal crosslinking agent) to be subjected to the polymerization reaction of the water absorbent resin.
[0136] (acrylic acid) In one embodiment of the present invention, from the viewpoint of the physical properties and productivity of the obtained water-absorbent resin, acrylic acid (alkali metal salt) is used as a monomer constituting the water-absorbent resin. The "acrylic acid" may be a known acrylic acid, and preferably contains methoxyphenols, more preferably p-methoxyphenol, as a polymerization inhibitor, preferably 200 ppm or less, more preferably 10 ppm or more to 160 ppm or less, and even more preferably 20 ppm or more to 100 ppm or less, from the viewpoint of the polymerizability of acrylic acid and the color tone of the water-absorbent resin. In addition, as for impurities in acrylic acid, the compounds described in U.S. Patent Application Publication No. 2008 / 0161512 are also applied to one embodiment of the present invention.
[0137] The "alkali metal salt of acrylic acid" is obtained by neutralizing the acrylic acid with the following basic composition. The alkali metal salt of acrylic acid may be a commercially available alkali metal salt of acrylic acid (e.g., sodium acrylate), or may be one obtained by neutralization in a production plant for a water absorbent resin.
[0138] (Basic Composition) In one embodiment of the present invention, the term "basic composition" refers to a composition containing a basic compound, and for example, a commercially available aqueous sodium hydroxide solution corresponds to the above. Specific examples of the basic compound include alkali metal salts such as carbonates and / or hydrogen carbonates of alkali metals, and hydroxides of alkali metals such as sodium hydroxide, potassium hydroxide, and lithium hydroxide. Among these, from the viewpoint of the physical properties of the obtained water absorbent resin, it is desirable that the composition is strongly basic. That is, hydroxides of alkali metals such as sodium hydroxide, potassium hydroxide, and lithium hydroxide are preferred, and sodium hydroxide is more preferred.
[0139] (neutralization) As the neutralization in one embodiment of the present invention, either neutralization of acrylic acid (before polymerization) or neutralization of a hydrogel-like crosslinked polymer obtained by crosslinking and polymerizing acrylic acid (after polymerization) (hereinafter referred to as "post-neutralization") can be selected or used in combination. When the recovered water-absorbent resin and / or its solubilized product are used as a part of the raw material (recycled raw material) for the production of a water-absorbent resin, if the recovered water-absorbent resin and / or its solubilized product contains a basic compound, this basic compound neutralizes the acrylic acid before polymerization or the hydrogel-like crosslinked polymer after polymerization. Therefore, as described later, the neutralization rate of the water-absorbent resin as a final product is adjusted to a predetermined range by adding this basic compound. In addition, these neutralizations may be continuous or batch-wise and are not particularly limited, but a continuous type is preferable from the viewpoint of production efficiency and the like. Regarding the conditions such as the neutralization apparatus, neutralization temperature, and residence time, the conditions described in International Publication No. 2009 / 123197 and US Patent Application Publication No. 2008 / 0194863 are also applied to the present invention.
[0140] In one embodiment of the present invention, the neutralization rate is preferably 10 mol% or more and 90 mol% or less, more preferably 40 mol% or more and 85 mol% or less, even more preferably 50 mol% or more and 80 mol% or less, and particularly preferably 60 mol% or more and 75 mol% or less, based on the acid group of the monomer. If the neutralization rate is 10 mol% or more, the recycled water absorbent resin obtained has excellent water absorption capacity, which is preferable. On the other hand, if the neutralization rate is 90 mol% or less, the recycled water absorbent resin having high water absorption capacity under pressure is obtained, which is preferable. Note that a neutralization rate of 75 mol% means a mixture of 25 mol% acrylic acid and 75 mol% alkali metal salt of acrylic acid. In addition, the mixture may be referred to as a partially neutralized product of acrylic acid.
[0141] The neutralization rate is the same in the case of post-neutralization. The neutralization rate is also applied to the neutralization rate of the recycled water absorbent resin as a final product. In the present invention, the recovered water absorbent resin and / or its solubilized product are used as a part of the raw material in the production of a water absorbent resin. When the recovered water absorbent resin and / or its solubilized product contain a basic compound, the neutralization of the acrylic acid (before polymerization) and / or the post-neutralization of the hydrogel-like crosslinked polymer are appropriately adjusted so that the neutralization rate of the recycled water absorbent resin as a final product, including the basic compound, falls within a predetermined range.
[0142] (Other monomers) In one embodiment of the present invention, the aqueous monomer solution may contain other monomers. The "other monomers" refers to monomers other than the acrylic acid (alkali metal salt), and the water absorbent resin can be produced by using the other monomers together with the acrylic acid (salt). The other monomers include water-soluble or hydrophobic unsaturated monomers. Specifically, the compounds described in U.S. Patent Application Publication No. 2005 / 0215734 (excluding acrylic acid) are also applicable to one embodiment of the present invention.
[0143] (Internal crosslinking agent) As the internal crosslinking agent used in one embodiment of the present invention, the compounds described in US Pat. No. 6,241,928 are also applied to one embodiment of the present invention. Among these, one or more compounds are selected in consideration of reactivity. In addition, from the viewpoint of the water absorption performance of the obtained recycled water absorbent resin, preferably a compound having two or more polymerizable unsaturated groups, more preferably a compound having thermal decomposition at the drying temperature described below, and even more preferably a compound having two or more polymerizable unsaturated groups having a (poly)alkylene glycol structural unit is used as the internal crosslinking agent. As the polymerizable unsaturated group, preferably an allyl group, a (meth)acrylate group, more preferably a (meth)acrylate group, can be mentioned. In addition, as the (poly)alkylene glycol structural unit, polyethylene glycol is preferable, and the number n is preferably 1 to 100, more preferably 6 to 50.
[0144] The amount of the internal crosslinking agent used is preferably 0.0001 mol% or more and 10 mol% or less, more preferably 0.001 mol% or more and 1 mol% or less, based on the total amount of monomers. By setting the amount used within the above range, a desired water-absorbing resin can be obtained. If the amount used is too small, the gel strength tends to decrease and the water-soluble content tends to increase, and if the amount used is too large, the water absorption capacity tends to decrease, which is not preferable.
[0145] In one embodiment of the present invention, a method is preferably applied in which a predetermined amount of an internal crosslinking agent is added to an aqueous monomer solution in advance, and a crosslinking reaction is carried out simultaneously with polymerization. On the other hand, in addition to this method, a method of post-crosslinking by adding an internal crosslinking agent during and / or after polymerization, a method of radical crosslinking using a radical polymerization initiator, a method of radiation crosslinking using active energy rays such as electron beams and ultraviolet rays, etc. can also be adopted. These methods can also be used in combination.
[0146] (Other substances added to the monomer aqueous solution) In one embodiment of the present invention, from the viewpoint of improving the physical properties of the resulting water-absorbent resin, the following substances may be added during preparation of the aqueous monomer solution.
[0147] Specifically, hydrophilic polymers such as starch, starch derivatives, cellulose, cellulose derivatives, polyvinyl alcohol, polyacrylic acid (alkali metal salt), and crosslinked polyacrylic acid (alkali metal salt) can be added at preferably 50% by mass or less, more preferably 20% by mass or less, even more preferably 10% by mass or less, and particularly preferably 5% by mass or less (lower limit: 0% by mass); foaming agents such as carbonates and bubbles, surfactants, chelating agents, chain transfer agents, etc. can be added at preferably 5% by mass or less, more preferably 1.0% by mass or less, and even more preferably 0.5% by mass or less (lower limit: 0% by mass). The above substances may be added not only to the aqueous monomer solution, but also during polymerization, or these forms may be used in combination.
[0148] When a water-soluble resin or a water-absorbent resin is used as the hydrophilic polymer, a graft polymer or a water-absorbent resin composition (e.g., a starch-acrylic acid polymer, a PVA-acrylic acid polymer, etc.) is obtained. These polymers and water-absorbent resin compositions are also within the scope of the present invention.
[0149] [3-1-6] Sulfite addition process The method for producing a recycled water absorbent resin according to one embodiment of the present invention more preferably includes an addition step of adding at least one selected from a sulfite and a hydrogen sulfite (hereinafter, sometimes referred to as "sulfite, etc.") to the hydrous gel-like crosslinked polymer and / or the polymer after the drying step. By adding a sulfite, etc., it is possible to reduce the amount of acrylic acid remaining in the water absorbent resin. Therefore, it is possible to reduce the acrylamide content in the recycled water absorbent resin.
[0150] The amount of sulfite and the like added to the hydrogel crosslinked polymer and / or the polymer after the drying step is preferably 0.0010% by mass to 1.0% by mass, more preferably 0.0030% by mass to 0.50% by mass, and even more preferably 0.0050% by mass to 0.30% by mass, in terms of the total amount added throughout the entire production method, relative to the finally obtained recycled water absorbent resin. As the sulfite and / or hydrogen sulfite, monovalent salts, particularly alkali metal salts such as sodium salts and potassium salts, can be preferably used.
[0151] In addition, the timing of carrying out this addition step, i.e., the timing of adding a sulfite or the like, is not particularly limited, and for example, it is preferable that this addition step is carried out between any of the steps of the polymerization step, the drying step, and the surface cross-linking step described above, and the gel crushing step, the crushing step, and the classification step described below.
[0152] [3-1-7] Amino polycarboxylic acid addition process The method for producing a recycled water absorbent resin according to one embodiment of the present invention further preferably includes an addition step of adding at least one selected from amino polycarboxylic acids and amino polyphosphoric acids (hereinafter, sometimes referred to as "amino polycarboxylic acids, etc."). By adding amino polycarboxylic acids, etc., it is possible to reduce the amount of acrylic acid remaining in the polymer. Therefore, it is possible to reduce the acrylamide content in the recycled water absorbent resin.
[0153] The amount of the amino polycarboxylic acid or the like to be added is preferably 0.00001% by mass or more and 10% by mass or less, more preferably 0.00005% by mass or more and 5% by mass or less, and even more preferably 0.0001% by mass or more and 1% by mass or less, based on the total amount added in the entire production method, relative to the finally obtained recycled water absorbent resin. Examples of the amino polycarboxylic acid and amino polyphosphoric acid are as described in the above section [2-6].
[0154] Examples of the method for adding the amino polycarboxylic acid etc. to the reaction system include, but are not limited to, a method in which the amino polycarboxylic acid etc. is added as is, a method in which the amino polycarboxylic acid etc. is added in the form of a solution or a slurry, and the like.
[0155] In the present production method, the timing of carrying out this addition step, i.e., the timing of adding the amino polyvalent carboxylic acid or the like, is not particularly limited, and for example, it is preferable that this addition step is carried out between any of the steps of the polymerization step, the drying step, and the surface crosslinking step described above, and the pulverization step and the classification step described below.
[0156] [3-1-8] Hydrogel crushing process The method for producing a recycled water absorbent resin according to one embodiment of the present invention may further include a hydrous gel crushing step in which the hydrous gel obtained in the polymerization step is crushed by a gel crusher such as a screw extruder such as a kneader or a meat chopper, or a cutter mill to obtain a particulate hydrous gel. When the polymerization step is kneader polymerization, the polymerization step and the gel crushing step are carried out simultaneously. In addition, when a particulate hydrous gel is directly obtained in the polymerization process, such as gas phase polymerization or reversed phase suspension polymerization, the gel crushing step may not be carried out. Regarding gel crushing conditions and forms other than those described above, the contents disclosed in International Publication No. 2011 / 126079 are preferably applied to the present invention.
[0157] [3-1-9] Grinding process, classification process The method for producing a recycled water absorbent resin according to one embodiment of the present invention may further include a step of pulverizing and / or classifying the polymer after the drying step, such as the dried polymer obtained in the drying step.
[0158] The pulverization process and the classification process are as explained in the above section [2-4-3], so the explanation will be omitted here.
[0159] [3-2] Embodiment 2 The method for producing a recycled water absorbent resin according to the present embodiment is a method for producing a recycled polyacrylic acid (alkali metal salt)-based water absorbent resin using a recovered water absorbent resin and / or a solubilized product thereof recovered from used absorbent articles or waste generated in the manufacturing process of the water absorbent resin as a part of a raw material, and includes a polymerization step for obtaining a polyacrylic acid (alkali metal salt)-based hydrogel-like crosslinked polymer containing the recovered water absorbent resin and / or a solubilized product thereof as a part of a raw material, a drying step for heating and drying the hydrogel-like crosslinked polymer, and a heat treatment step for heat treating the polymer after the drying step, if necessary, in which the nitrogen content contained in the recovered water absorbent resin and / or the solubilized product thereof used as the raw material is 1.0 mass% or less (based on solid content) and the residual acrylic acid content of the recycled water absorbent resin is 300 ppm or less.
[0160] The by-production of acrylamide in the production of recycled water absorbent resin may occur due to the reaction between acrylic acid, which is a remaining monomer component, and nitrogen content. Therefore, by controlling the nitrogen content, which is a causative substance of acrylamide by-product, contained in the recovered water absorbent resin and / or its solubilized product used as a part of the raw material, and by making the residual acrylic acid content of the obtained recycled water absorbent resin 300 ppm or less, a recycled water absorbent resin having an acrylamide content below the detection limit (0.1 ppm) can be obtained.
[0161] In the method for producing a recycled water absorbent resin according to the present embodiment, the nitrogen content of the recovered water absorbent resin and / or its solubilized product is 1.0 mass % or less, more preferably 0.9 mass % or less, and further preferably 0.8 mass % or less.
[0162] In the method for producing a recycled water absorbent resin according to the present embodiment, the content of residual acrylic acid in the recycled water absorbent resin is 300 ppm or less, more preferably 200 ppm or less, and further preferably 100 ppm or less.
[0163] In the production method according to the present embodiment, if the nitrogen content contained in the recovered water absorbent resin and / or the solubilized product thereof is 1.0 mass % or less (based on the solid content) and the residual acrylic acid content of the recycled water absorbent resin is 300 ppm or less, the heating conditions in the production process of the recycled water absorbent resin may be normal conditions, but are more preferably mild conditions, and the heating time during which the material temperature exceeds 140° C. after the drying process is 60 minutes or less, more preferably 45 minutes or less, and even more preferably 30 minutes or less.
[0164] The configuration of the production method according to the present embodiment is the same as that of the first embodiment, except for the nitrogen content contained in the recovered water absorbent resin and / or the solubilized product thereof, the residual acrylic acid content of the recycled water absorbent resin, and the heating conditions in the production process of the recycled water absorbent resin.
[0165] [3-3] Embodiment 3 The method for producing a recycled water absorbent resin according to the present embodiment is a method for producing a recycled polyacrylic acid (alkali metal salt)-based water absorbent resin using a recovered water absorbent resin recovered from used absorbent articles or waste generated in the process of producing a water absorbent resin, and / or a solubilized product thereof as part of a raw material, and includes a step of measuring the acrylamide content in the recycled water absorbent resin, and a step of sorting the recycled water absorbent resin based on the acrylamide content.
[0166] Here, the method for the "step of measuring the acrylamide content in the recycled water absorbent resin" is not particularly limited as long as the method can measure the acrylamide content. For example, the method described in the Examples can be suitably adopted.
[0167] "Sorting the recycled water absorbent resin according to the acrylamide content" means, for example, sorting the recycled water absorbent resin as a reusable recycled water absorbent resin if the acrylamide content is less than the detection limit (0.1 ppm), and sorting the recycled water absorbent resin as a defective product that cannot be reused if the acrylamide content is equal to or greater than the detection limit (0.1 ppm).
[0168] According to the manufacturing method of the recycled water absorbent resin of the present embodiment, even when a recycled water absorbent resin containing acrylamide on the order of several ppm is manufactured, such recycled water absorbent resin is removed as a defective product that cannot be reused, and thus a highly safe recycled water absorbent resin can be provided.
[0169] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. EXAMPLES
[0170] The present invention will be described in more detail with reference to the following examples and comparative examples. However, the present invention is not limited to these examples. Examples obtained by appropriately combining the technical means disclosed in each example are also included in the scope of the present invention.
[0171] [Measurement and evaluation method] (a) Urea content 200.0 g of 0.90% by mass sodium chloride aqueous solution was weighed out into a 250 ml plastic container with a lid, 1.00 g of water absorbent resin was added to the aqueous solution, and the mixture was stirred for 16 hours with a stirrer. By this operation, urea contained in the water absorbent resin was extracted.
[0172] Subsequently, the obtained extract was filtered through a filter (pore size: 0.45 μm), and the obtained filtrate was analyzed by high performance liquid chromatography (HPLC) to quantitatively determine the urea content in the water-absorbent resin.
[0173] (b) CRC (ERT441.2-02) "CRC" of a water-absorbent resin is an abbreviation for "Centrifuge Retention Capacity," and indicates the absorption capacity (unit: g / g) of a water-absorbent resin for 30 minutes under no pressure in a 0.90 mass % sodium chloride aqueous solution.
[0174] Specifically, 0.200 g of the water-absorbent resin was uniformly placed in a bag (85 mm x 60 mm) made of nonwoven fabric (manufactured by Nangoku Pulp Industrial Co., Ltd., product name: Heatlon Paper, model: GSP-22), heat-sealed, and then immersed in a large excess (usually about 500 ml) of 0.90% by mass sodium chloride aqueous solution at room temperature. After 30 minutes, the bag was pulled out and drained for 3 minutes at a centrifugal force (250 G) described in ERT441.2-02 using a centrifuge (manufactured by Kokusan Co., Ltd., centrifuge: model H-122), and the mass W1 (g) of the bag was measured. In addition, the same operation was performed without using the water-absorbent resin, and the mass W0 (g) at that time was measured. Then, from these W1 and W0, the CRC (centrifuge retention capacity) was calculated according to the following formula (1).
[0175] CRC(g / g)=(W1-W0) / (mass of water-absorbent resin)-1···Equation (1) (c) AAP0.3 The "AAP" of a water-absorbent resin is an abbreviation for "Absorption Against Pressure" and indicates the absorbency (unit: g / g) against a 0.90% by mass aqueous sodium chloride solution. Also, "AAP0.3" means the AAP under a pressure of 0.3 psi.
[0176] Specifically, the AAP0.3 of the water-absorbent resin (recycled water-absorbent resin) was measured in accordance with NWSP 242.0.R2(15) except that the pressure condition was changed from 0.7 psi to 0.3 psi. More specifically, a large excess of 0.9 mass% sodium chloride aqueous solution was used, and 0.9 g of the water-absorbent resin was subjected to pressure of 2.07 kPa (21 g / cm) for 1 hour. 2 After swelling under a pressure of 0.2 psi (0.3 psi), the AAP (absorbency against pressure) was measured.
[0177] (d) Color tone The colored state of the water-absorbent resin after drying was visually observed.
[0178] (e) Residual monomer content (residual acrylic acid content) (ERT410.2-02) The amount of residual monomers in the water absorbent resin was quantified according to ERT410.2-02 (Residual Monomers).
[0179] Specifically, 1.0 g of the water-absorbent resin is dissolved in 200 cm of a 0.90% by mass aqueous solution of sodium chloride. 3 (temperature: 23±2° C.), stirred at 500±50 rpm for 1 hour, and then filtered. The amount of residual monomer in the obtained filtrate was measured by HPLC.
[0180] (f) Residual acrylamide content The filtrate obtained during the measurement of the amount of residual monomer (e) was concentrated as necessary, and the content of residual acrylamide was measured by HPLC.
[0181] (g) Nitrogen content Regarding the nitrogen content contained in the recovered water absorbent resin and / or its solubilized matter, the nitrogen content derived from urea was determined by liquid chromatography, and the nitrogen content derived from ammonia was determined by the indophenol method.
[0182] [Production Example 1] A reaction solution was prepared by dissolving 0.44 parts by mass of polyethylene glycol diacrylate (molecular weight: 523) in 550 parts by mass of a 38% by mass aqueous solution of sodium acrylate (neutralization rate: 71 mol%), and then degassing the reaction solution for 30 minutes under a nitrogen gas atmosphere.
[0183] Next, the reaction liquid was fed into a jacketed stainless steel twin-arm kneader having two sigma-type blades with an openable lid, and the inside of the system was purged with nitrogen gas while maintaining the reaction liquid at 30°C.
[0184] Next, 0.24 parts by mass of ammonium persulfate and 0.012 parts by mass of L-ascorbic acid were added to the reaction solution while stirring, and polymerization started about 1 minute later. Polymerization was then carried out at 30° C. to 95° C., and a hydrogel-like crosslinked polymer (hereinafter referred to as "hydrogel") was taken out 60 minutes after the start of polymerization.
[0185] The obtained hydrogel was dried with hot air at 150° C. for 100 minutes, pulverized in a vibration mill, and further classified with JIS standard sieves with mesh sizes of 850 μm and 106 μm to obtain an irregularly pulverized water-absorbent resin precursor.
[0186] 100 parts by mass of the obtained water absorbent resin precursor was mixed with a surface cross-linking agent composition liquid consisting of 0.03 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol, and 3.15 parts by mass of water.
[0187] The mixture thus obtained was heat-treated at 100° C. for 45 minutes to obtain a white water-absorbing resin (M1). The water-absorbing resin (M1) had a mass average particle size of 400 μm, a water-soluble component content of 9 mass%, a CRC of 41.7 g / g, and an AAP0.3 of 30.7 g / g.
[0188] Next, 20.0 g of the water absorbent resin (M1) was placed in a beaker, and 600.0 g of artificial urine (1.90 mass% urea, 0.80 mass% sodium chloride, 0.10 mass% magnesium chloride hexahydrate, 0.10 mass% calcium chloride dihydrate, 97.10 mass% ion-exchanged water) was added thereto. After that, the mixture was left for 24 hours to obtain a simulated used water absorbent resin (1).
[0189] [Reference example 1] Into a beaker, 620 g of the simulated used water absorbent resin (1) obtained in Production Example 1 and 1800.0 g of ion-exchanged water were added and stirred for 15 minutes (water washing treatment: 1st time), and then the content of the beaker was filtered through a 100 mesh (150 μm mesh) stainless steel wire mesh.
[0190] 1956.5 g of the filtrate after the water washing treatment obtained in the filtration was returned to the beaker, 1900.0 g of acetone was added thereto, and the mixture was stirred for 15 minutes (dehydration treatment), and then the content of the beaker was filtered through a 100 mesh stainless steel wire screen.
[0191] Next, 104.2 g of the filtrate after the dehydration treatment obtained by the filtration was dried in an oven at 180°C for 3 hours, pulverized in a vibration mill, and further classified using JIS standard sieves with openings of 850 μm and 106 μm to obtain an irregularly crushed recovered water absorbent resin precursor (S1).
[0192] 100 parts by mass of the obtained recovered water absorbent resin precursor (S1) was uniformly mixed with a surface crosslinking agent solution consisting of 0.03 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol, and 3.15 parts by mass of water, and the mixture was heated at 100° C. for 45 minutes. As a result, a recovered water absorbent resin (S1) was obtained.
[0193] The recovered water absorbent resin (S1) thus obtained had a urea content of 1.5 mass%, a CRC of 40.0 g / g, an AAP0.3 of 29.1 g / g, a nitrogen content derived from ammonia of 0.8 mass%, a residual acrylic acid content of 180 ppm, and a white color after drying.
[0194] [Reference example 2] 620 g of the simulated used water absorbent resin (1) obtained in Production Example 1 and 1,800.0 g of ion-exchanged water were added to a beaker and stirred for 15 minutes (water washing treatment: first time), and then the content of the beaker was filtered through a 100-mesh stainless steel wire screen.
[0195] The filtrate (1,956.5 g) obtained after the water washing treatment in the filtration was returned to the beaker, and 1,800.0 g of fresh ion-exchanged water was added thereto and stirred for 15 minutes (water washing treatment: second time), after which the contents of the beaker were filtered through a 100-mesh stainless steel wire mesh.
[0196] The filtrate (2764.8 g) obtained after the second water washing treatment in the filtration was returned to the beaker, and 2800.0 g of acetone was added thereto and stirred for 15 minutes (dehydration treatment), after which the contents of the beaker were filtered through a 100 mesh stainless steel wire mesh.
[0197] Next, 88.1 g of the filtrate after the dehydration treatment obtained by the filtration was dried in an oven at 180°C for 3 hours, then pulverized in a vibration mill and further classified using JIS standard sieves with openings of 850 μm and 106 μm to obtain an irregularly crushed recovered water absorbent resin precursor (S2).
[0198] 100 parts by mass of the obtained recovered water absorbent resin precursor (S2) was uniformly mixed with a surface crosslinking agent solution consisting of 0.03 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol, and 3.15 parts by mass of water, and the mixture was heated at 100° C. for 45 minutes. As a result, a recovered water absorbent resin (S2) was obtained.
[0199] The recovered water absorbent resin (S2) thus obtained had a urea content of 0.6% by mass, a CRC of 41.1 g / g, an AAP0.3 of 29.5 g / g, a nitrogen content derived from ammonia of 0.3% by mass, a residual acrylic acid content of 150 ppm, and a white color after drying.
[0200] [Reference example 3] A recovered water absorbent resin (S3) was obtained by carrying out drying, pulverization, classification and surface crosslinking in the same manner as in Reference Example 1, except that the water washing treatment and dehydration treatment in Reference Example 1 were not carried out.
[0201] The recovered water absorbent resin (S3) thus obtained had a urea content of 29.0% by mass, a CRC of 24.3 g / g, an AAP0.3 of 16.4 g / g, a nitrogen content derived from ammonia of 14.5% by mass, and a residual acrylic acid content of 440 ppm, and had a yellowish color after drying.
[0202] [Table 1]
[0203] Table 1 shows the results of evaluation of the recovered water absorbent resins (S1) to (S3) obtained in Reference Examples 1 to 3 with respect to the urea content, CRC, AAP0.3, and color tone after drying.
[0204] [Production Example 2] 620 g of the simulated used water absorbent resin (1) obtained in Production Example 1 and 1,800.0 g of ion-exchanged water were added to a beaker and stirred for 15 minutes (water washing treatment: first time), and then the content of the beaker was filtered through a 100-mesh stainless steel wire screen.
[0205] 1942.5 g of the filtrate after the water washing treatment obtained by the filtration was returned to the beaker, 1900.0 g of acetone was added thereto, and the mixture was stirred for 15 minutes (dehydration treatment), after which the beaker contents were filtered through a 100 mesh stainless steel wire screen. The urea content of the filtrate after the dehydration treatment obtained by the filtration was measured and found to be 1.5 mass%.
[0206] Subsequently, 106.4 g of the filtrate after the dehydration treatment was returned to the beaker, 100 g of ion-exchanged water was added thereto, and the temperature was raised to 80° C. with stirring. Thereafter, 1.43 g of a 30 mass % aqueous hydrogen peroxide solution, 0.050 g of iron (II) sulfate heptahydrate, 1.00 g of L-ascorbic acid, and 3.00 g of sulfuric acid were added to initiate decomposition of the simulated used water absorbent resin (1).
[0207] After 90 minutes, the aqueous solution was filtered through a 100-mesh stainless steel wire screen to obtain an aqueous solution of solubilized polymer (1) in which the simulated used water absorbent resin (1) was solubilized. The mass-average molecular weight of the solubilized polymer (1) was 108,000.
[0208] The insoluble matter remaining on the stainless steel wire net during the filtration was thoroughly washed with ion-exchanged water, and then dried together with the stainless steel wire net in an oven at 180° C. for 2 hours. The decomposition rate of the water-absorbent resin was calculated according to the following formula (3) and was found to be 99.7%.
[0209] Decomposition rate of water-absorbent resin (%) = [1 - {(mass of stainless steel wire mesh and insoluble matter after drying) - (mass of stainless steel wire mesh)} / (mass of water-absorbent resin before decomposition)] × 100 (2) Finally, the aqueous solution of the solubilized polymer (1) was concentrated with an evaporator to obtain a solubilized polymer concentrate (1) having a solid content of 21.1% by mass. The solubilized polymer (1) had a urea content of 1.4% by mass, a nitrogen content derived from ammonia of 0.7% by mass, and a residual acrylic acid content of 20 ppm, based on the solid content.
[0210] [Production Example 3] The urea content of the simulated used water absorbent resin (1) obtained in Production Example 1 was measured and found to be 28.8% by mass.
[0211] Next, 620.0 g of the simulated used water absorbent resin (1) was placed in a beaker, 400.0 g of ion-exchanged water was added thereto, and the temperature was raised to 80° C. while stirring. Then, 1.43 g of a 30 mass% aqueous hydrogen peroxide solution, 0.050 g of iron (II) sulfate heptahydrate, 1.00 g of L-ascorbic acid, and 3.00 g of sulfuric acid were added to start decomposition of the simulated used water absorbent resin (1).
[0212] After 90 minutes, the aqueous solution was filtered through a 100-mesh stainless steel wire screen to obtain an aqueous solution of solubilized polymer (2) in which the simulated used water absorbent resin (1) was solubilized. The mass average molecular weight of the solubilized polymer (2) was 108,000. The decomposition rate of the water absorbent resin was determined in the same manner as in Production Example 2, and was 99.4%.
[0213] Finally, the aqueous solution of the solubilized polymer (2) was concentrated by an evaporator to obtain a solubilized polymer concentrate (2) having a solid content of 21.2% by mass. The solubilized polymer (2) had a urea content of 27.1% by mass, a nitrogen content derived from ammonia of 13.8% by mass, and a residual acrylic acid content of 30 ppm, based on the solid content.
[0214] [Comparative Example 1] An aqueous monomer solution (1) was prepared by dissolving 0.42 parts by mass of polyethylene glycol diacrylate (molecular weight: 523) in 539.6 parts by mass of a 36.8% by mass aqueous solution of sodium acrylate (neutralization rate: 71 mol%).
[0215] Next, the above-mentioned aqueous monomer solution (1) and 10.5 parts by mass of the recovered water absorbent resin (S1) (urea content: 1.5% by mass) obtained in Reference Example 1 were fed into a jacketed stainless steel double-arm kneader having two sigma-type blades and an openable lid, and the liquid temperature in the kneader was kept at 30°C and replaced with nitrogen gas for 30 minutes.
[0216] Next, 0.24 parts by mass of ammonium persulfate and 0.012 parts by mass of L-ascorbic acid were added while stirring the liquid in the kneader, and polymerization started about 1 minute later. Polymerization was continued at 30° C. or higher and 95° C. or lower, and the hydrogel (1) was taken out 60 minutes after the start of polymerization.
[0217] The obtained hydrogel (1) was dried with hot air at 150°C (material temperature) for 100 minutes, pulverized with a vibration mill, and further classified with JIS standard sieves with mesh sizes of 850μm and 106μm to obtain a recycled water-absorbent resin precursor (C1) using the recovered water-absorbent resin (S1). The obtained recycled water-absorbent resin precursor (C1) had a residual acrylic acid content of 500ppm, an acrylamide content of 0.3ppm, and a nitrogen content (derived from urea and ammonia) of 0.2% by mass.
[0218] [Comparative Example 2] In Comparative Example 1, the same operation as in Comparative Example 1 was performed except that 10.5 parts by mass of the recovered water absorbent resin (S3) (urea content 29.0% by mass) obtained in Reference Example 3 was supplied instead of 10.5 parts by mass of the recovered water absorbent resin (S1) (urea content 1.5% by mass) obtained in Reference Example 1, to obtain a recycled water absorbent resin precursor (C2) using the recovered water absorbent resin (S3). The obtained recycled water absorbent resin precursor (C2) had an acrylamide content of 0.4 ppm, a nitrogen content (derived from urea and ammonia) of 1.4% by mass, and a residual acrylic acid content of 450 ppm.
[0219] [Comparative Example 3] In Comparative Example 1, the same operation as in Comparative Example 1 was performed except that 10.5 parts by mass of the recovered water absorbent resin (S2) (urea content 0.6% by mass) obtained in Reference Example 2 was supplied instead of 10.5 parts by mass of the recovered water absorbent resin (S1) (urea content 1.5% by mass) obtained in Reference Example 1, to obtain a recycled water absorbent resin precursor (C3) using the recovered water absorbent resin (S2). The obtained recycled water absorbent resin precursor (C3) had an acrylamide content of 0.1 ppm, a nitrogen content (derived from urea and ammonia) of 0.1% by mass, and a residual acrylic acid content of 480 ppm.
[0220] [Comparative Example 4] In Comparative Example 1, the same operation as in Comparative Example 1 was performed except that 10.5 parts by mass of the recovered water absorbent resin (S1) (urea content 1.5% by mass) obtained in Reference Example 1 was not supplied, to obtain a water absorbent resin precursor (C4). The obtained water absorbent resin precursor (C4) had an acrylamide content of ND (<0.1 ppm), a nitrogen content (derived from urea and ammonia) of ND (less than 0.1% by mass), and a residual acrylic acid content of 440 ppm. Here, ND means less than the detection limit.
[0221] [Example 1] A recycled water absorbent resin precursor (1) was obtained using the recovered water absorbent resin by performing the same operation as in Comparative Example 1, except that the hot air drying conditions were changed from "150°C (material temperature) for 100 minutes" to "160°C (material temperature) for 30 minutes" in Comparative Example 1. The resulting recycled water absorbent resin precursor (1) had a residual monomer content of 250 ppm, an acrylamide content of ND (<0.1 ppm), a nitrogen content (derived from urea and ammonia) of 0.2 mass%, and a residual acrylic acid content of 250 ppm.
[0222] [Example 2] In Example 1, sodium sulfite was added to the hydrogel (1) in an amount of 0.2% by mass based on solid content, mixed, and then aged at 60° C. for 1 hour, followed by drying with hot air at 150° C. (material temperature) for 60 minutes, to obtain a recycled water-absorbent resin precursor (2) using a recovered water-absorbent resin, in the same manner as in Example 1. The obtained recycled water-absorbent resin precursor (2) had a residual monomer content of 150 ppm, an acrylamide content of ND (<0.1 ppm), a nitrogen content (derived from urea and ammonia) of 0.2% by mass, and a residual acrylic acid content of 150 ppm.
[0223] [Comparative Example 5] A monomer aqueous solution (2) was prepared by dissolving 0.42 parts by mass of polyethylene glycol diacrylate (molecular weight: 523) in 522.5 parts by mass of a 38% by mass aqueous solution of sodium acrylate (neutralization rate: 71 mol%).
[0224] Next, the above-mentioned aqueous monomer solution (2) and 50.0 parts by mass of the solubilized polymer concentrate (1) (urea content: 2.0% by mass) obtained in Production Example 2 were fed into a jacketed stainless steel twin-arm kneader having two sigma-type blades with an openable lid, and the liquid temperature in the kneader was kept at 30°C while the nitrogen gas was replaced for 30 minutes.
[0225] Next, 0.24 parts by mass of ammonium persulfate and 0.012 parts by mass of L-ascorbic acid were added while stirring the liquid in the kneader, and polymerization started about 1 minute later. Polymerization was then continued at 30° C. or higher and 95° C. or lower, and a hydrogel (C5) was taken out 60 minutes after the start of polymerization.
[0226] The obtained hydrogel (C5) was dried with hot air at 150°C (material temperature) for 100 minutes, pulverized with a vibration mill, and further classified with JIS standard sieves with mesh sizes of 850μm and 106μm to obtain a recycled water-absorbent resin precursor (C5). The obtained recycled water-absorbent resin precursor (C5) had an acrylamide content of 0.3ppm, a nitrogen content (derived from urea and ammonia) of 0.8% by mass, and a residual acrylic acid content of 400ppm.
[0227] [Comparative Example 6] A recycled water absorbent resin precursor (C6) was obtained by carrying out the same operation as in Comparative Example 5, except that the solubilized polymer concentrate (2) (urea content 28.8 mass%) obtained in Production Example 3 was supplied instead of the solubilized polymer concentrate (1) obtained in Production Example 2. The obtained recycled water absorbent resin precursor (C6) had an acrylamide content of 0.4 ppm, a nitrogen content (derived from urea and ammonia) of 14.3 mass%, and a residual acrylic acid content of 350 ppm.
[0228] [Comparative Example 7] A water absorbent resin precursor (C7) was obtained by the same operation as in Comparative Example 5, except that the solubilized polymer concentrate (1) obtained in Production Example 2 was not supplied. The obtained water absorbent resin precursor (C7) had an acrylamide content of ND (<0.1 ppm), a nitrogen content (derived from urea and ammonia) of ND (less than 0.1 mass%), and a residual acrylic acid content of 460 ppm.
[0229] [Example 3] A recycled water absorbent resin precursor (3) was obtained by the same operation as in Comparative Example 5, except that the hot air drying conditions were changed from "150°C (material temperature) for 100 minutes" to "160°C (material temperature) for 30 minutes" in Comparative Example 5. The obtained recycled water absorbent resin precursor (3) had an acrylamide content of ND (<0.1 ppm), a nitrogen content (derived from urea and ammonia) of 0.2 mass%, and a residual acrylic acid content of 240 ppm.
[0230] [Comparative Example 8] A surface crosslinking agent solution consisting of 0.5 parts by mass of ethylene carbonate and 2 parts by mass of water was uniformly mixed with 100 parts by mass of the recycled water absorbent resin precursor (C1) obtained in Comparative Example 1, and the mixture was heated at 180°C (material temperature) for 60 minutes. As a result, a recycled water absorbent resin (C8) was obtained.
[0231] The obtained recycled water absorbent resin (C8) had an acrylamide content of 2.4 ppm, a nitrogen content (derived from urea and ammonia) of 0.3 mass %, and a residual acrylic acid content of 320 ppm.
[0232] [Comparative Example 9] A surface crosslinking agent solution consisting of 0.1 parts by mass of ethylene glycol diglycidyl ether and 2 parts by mass of water was uniformly mixed with 100 parts by mass of the recycled water absorbent resin precursor (C1) obtained in Comparative Example 1, and the mixture was heat-treated at 120°C (material temperature) for 30 minutes. As a result, a recycled water absorbent resin (C9) was obtained.
[0233] The obtained recycled water absorbent resin (C9) had an acrylamide content of 0.3 ppm, a nitrogen content (derived from urea and ammonia) of 0.2 mass %, and a residual acrylic acid content of 390 ppm.
[0234] [Example 4] 100 parts by mass of the recycled water absorbent resin precursor (1) obtained in Example 1 was uniformly mixed with a surface crosslinking agent solution consisting of 0.1 parts by mass of ethylene glycol diglycidyl ether and 2 parts by mass of water, and the mixture was heated at 120°C (material temperature) for 30 minutes to obtain a recycled water absorbent resin (4).
[0235] The resulting recycled water absorbent resin (4) had an acrylamide content of ND (<0.1 ppm), a nitrogen content (derived from urea and ammonia) of ND (less than 0.1 mass%), and a residual acrylic acid content of 280 ppm.
[0236] [Table 2]
[0237] [Table 3]
[0238] (summary) The measurement results of the amount of acrylamide contained in the recycled water absorbent resin precursor and the water absorbent resin precursor obtained in Comparative Examples 1 to 7 and Examples 1 to 3, and the recycled water absorbent resin obtained in Comparative Examples 8, 9, and Example 4 are shown in Tables 2 and 3.
[0239] From a comparison between Comparative Examples 1 to 3 in which the recovered water absorbent resin was used as a raw material and Comparative Example 4 in which the recovered water absorbent resin was not used as a raw material, it can be seen that even when acrylamide is not used as a raw material, when the recovered water absorbent resin is used as a raw material, acrylamide is by-produced in the obtained recycled water absorbent resin precursor on the order of 0.1 ppm or more and 0.4 ppm or less.
[0240] Comparing the drying conditions of the hydrous gel in Comparative Example 1 (material temperature 150°C / drying time 100 minutes), Example 1 (material temperature 160°C / drying time 30 minutes), and Example 2 (material temperature 150°C / drying time 60 minutes), it can be seen that when the material temperature is high, particularly when the material temperature exceeds 140°C, shortening the drying time is effective in reducing the acrylamide content in the recycled water absorbent resin (ND (<0.1 ppm)).
[0241] Moreover, in Example 2 in which sulfite was added (residual monomer amount: 150 ppm), the amount of residual monomer (residual acrylic acid) was reduced compared to Comparative Example 1 in which sulfite was not added (residual monomer amount: 500 ppm) and Example 1 in which sulfite was not added (residual monomer amount: 250 ppm). This shows that the reduction in the amount of residual monomer (residual acrylic acid) by adding sulfite is effective in reducing the acrylamide content in the recycled water absorbent resin (ND (<0.1 ppm)).
[0242] Regarding the case where the solubilized product of the recovered water absorbent resin was used as the raw material, a comparison between Comparative Examples 5 and 6 in which the solubilized product of the recovered water absorbent resin was used as the raw material and Comparative Example 7 in which the solubilized product of the recovered water absorbent resin was not used as the raw material shows that even in the case where acrylamide is not used as the raw material, when the solubilized product of the recovered water absorbent resin is used as the raw material, acrylamide is by-produced in the obtained recycled water absorbent resin precursor on the order of 0.3 ppm or more and 0.4 ppm or less.
[0243] In addition, by comparing Comparative Example 1, in which the drying conditions for the hydrous gel were material temperature 150°C / drying time 100 minutes, with Example 3, in which the drying conditions were material temperature 160°C / drying time 30 minutes, it can be seen that when the material temperature is high, particularly when the material temperature exceeds 140°C, shortening the drying time is effective in reducing the acrylamide content in the recycled water absorbent resin (ND (<0.1 ppm)).
[0244] In addition, even if the same recycled water absorbent resin precursor (C1) was used as a raw material from the same recovered water absorbent resin (S1), the acrylamide content in the obtained recycled water absorbent resin was significantly increased by the surface crosslinking treatment at high temperature and for a long time, as compared with the recycled water absorbent resin (C8) obtained in Comparative Example 8, in which the heating conditions for the surface crosslinking treatment were 180°C and 60 minutes, and the recycled water absorbent resin (C9) obtained in Comparative Example 9, in which the heating conditions for the surface crosslinking treatment were 120°C and 30 minutes. Specifically, the acrylamide content of the same recycled water absorbent resin precursor (C1) used as a raw material was 0.3 ppm, but in the recycled water absorbent resin (C8) obtained in Comparative Example 8, it increased to 2.4 ppm. On the other hand, in the recycled water absorbent resin (C8) obtained in Comparative Example 9, there was no increase in the acrylamide content, and it was 0.3 ppm.
[0245] The mechanism of acrylamide by-production by use of recovered water absorbent resin, which has been discovered for the first time, is presumed to be that urea and ammonia, which is a decomposition product of urea, contained in used water absorbent resin react with acrylic acid, which is a raw material of water absorbent resin, to generate acrylamide. In order to suppress such a side reaction, the present invention reduces the amount of urea and ammonia, and also reduces the amount of residual monomer (residual acrylic acid), which is a raw material of acrylamide, by controlling the temperature and reducing the amount of residual monomer (residual acrylic acid), which is a raw material of acrylamide, thereby achieving an acrylamide content of ND (<0.1 ppm). [Industrial Applicability]
[0246] According to the recycled water absorbent resin and the manufacturing method thereof according to one embodiment of the present invention, when recycling a water absorbent resin that has absorbed a liquid to be absorbed such as urine and swelled, it is possible to solve the problem that acrylamide, which is an impurity not contained in normal (non-recycled) water absorbent resin, may be contained in the recycled water absorbent resin on the order of several ppm. Therefore, the present invention can be suitably used for recycling water absorbent resins and the like recovered from used absorbent articles, and is very useful.
Claims
1. A recycled polyacrylic acid (alkali metal salt)-based water absorbent resin, which is made of a recovered water absorbent resin and / or a solubilized product thereof recovered from used absorbent articles or waste generated in the manufacturing process of the water absorbent resin, A recycled water-absorbent resin having a residual acrylamide content below the detection limit (0.1 ppm).
2. 2. The recycled water absorbent resin according to claim 1, which contains at least one polyvalent metal cation selected from calcium and magnesium in a total amount of 1 ppm to 1000 ppm inside the resin.
3. 2. The recycled water absorbent resin according to claim 1, further comprising at least one selected from the group consisting of sulfite and hydrogen sulfite.
4. The recycled water-absorbing resin according to claim 1, wherein the resin contains more than 0% by mass and not more than 1.0% by mass of nitrogen.
5. 2. The recycled water absorbent resin according to claim 1, wherein the residual acrylic acid content is 300 ppm or less.
6. The recycled water absorbent resin according to claim 1, having a moisture content of 3% by mass or more and 15% by mass or less.
7. 2. The recycled water absorbent resin according to claim 1, comprising at least one selected from the group consisting of amino polyvalent carboxylic acids and amino polyvalent phosphoric acids.
8. A method for producing a recycled polyacrylic acid (alkali metal salt)-based water absorbent resin, comprising the steps of: recovering a water absorbent resin recovered from used absorbent articles or waste generated in the process of producing a water absorbent resin; and / or a solubilized product thereof as a part of a raw material, The method includes a polymerization step of obtaining a polyacrylic acid (alkali metal salt)-based hydrogel crosslinked polymer containing the recovered water-absorbent resin and / or its solubilized product as a part of a raw material, a drying step of heating and drying the hydrogel crosslinked polymer, and a heat treatment step of heat-treating the polymer after the drying step, if necessary. The nitrogen content contained in the recovered water absorbent resin and / or its solubilized product used as the raw material is 1.0 mass% or less (based on solid content), The method for producing a recycled water absorbent resin, wherein the heating time during which the material temperature exceeds 140° C. is 60 minutes or less after the drying step.
9. The method according to claim 8, further comprising the step of adding at least one selected from a sulfite and a hydrogen sulfite to the hydrogel-like crosslinked polymer and / or the polymer after the drying step.
10. The method according to claim 8, wherein the recycled water absorbent resin has a residual acrylic acid content of 300 ppm or less.
11. The method according to claim 8 , wherein the drying step and the heat treatment step are performed such that the polymer has a water content in the range of 3% by mass or more and 15% by mass or less after each of these steps.
12. The manufacturing method according to claim 8, wherein the recovered water absorbent resin and / or its solubilized product used as the raw material contains at least one polyvalent metal cation selected from calcium and magnesium in a total amount of 1 ppm to 1000 ppm inside the resin.
13. The method according to claim 8, further comprising the step of adding at least one selected from the group consisting of amino polycarboxylic acids and amino polyphosphoric acids.
14. The method according to claim 8, wherein the recovered water absorbent resin and / or its solubilized product used as the raw material has an ammonia-derived nitrogen content of 1.0 mass % (based on solid content) or less.
15. A method for producing a recycled polyacrylic acid (alkali metal salt)-based water absorbent resin, comprising the steps of: recovering a water absorbent resin recovered from used absorbent articles or waste generated in the process of producing a water absorbent resin; and / or a solubilized product thereof as a part of a raw material, The method includes a polymerization step of obtaining a polyacrylic acid (alkali metal salt)-based hydrogel crosslinked polymer containing the recovered water-absorbent resin and / or its solubilized product as a part of a raw material, a drying step of heating and drying the hydrogel crosslinked polymer, and a heat treatment step of heat-treating the polymer after the drying step, if necessary. The nitrogen content contained in the recovered water absorbent resin and / or its solubilized material used as the raw material is 1.0 mass% or less (based on solid content), A method for producing a recycled water absorbent resin, wherein the recycled water absorbent resin has a residual acrylic acid content of 300 ppm or less.
16. The method according to claim 15, further comprising the step of adding at least one selected from a sulfite and a hydrogen sulfite to the hydrogel-like crosslinked polymer and / or the polymer after the drying step.
17. A method for producing a recycled polyacrylic acid (alkali metal salt)-based water absorbent resin, comprising the steps of: recovering a water absorbent resin recovered from used absorbent articles or waste generated in the process of producing a water absorbent resin; and / or a solubilized product thereof as a part of a raw material, A method for producing a recycled water absorbent resin, comprising: a step of measuring an acrylamide content in a recycled water absorbent resin; and a step of selecting the recycled water absorbent resin based on the acrylamide content.
Citation Information
Patent Citations
Method for producing water-absorbing resin particles
WO2020213298A1
Method for producing recycled superabsorbent polymer, method for producing superabsorbent polymer using recycled superabsorbent polymer, and recycled superabsorbent polymer
WO2021044690A1
Recycling of superabsorbent polymer with an extensional flow device
WO2021257431A1
Method for producing water-absorbing resin particles
WO2022080342A1